Genome-wide association study reveals acute mountain sickness susceptibility in Chinese population - Xiangyi Zheng; Wenyu Song; Yuanfeng Li; Nandi Bao; Wenhui Li; Yang Liu; Juanjuan Liu; Bin Li; Xi Yang; Xiaobo Han; Jialin Wu; Liqun Ma; et al. (Molecular Genetics and Genomics, 2026)

Correction to: Spil mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Spil-mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

​​Integrating machine learning and spatial transcriptomics uncovers shared immunomodulatory deubiquitinases in MAFLD and HCC - Yu-xi Han; Hongze Li; Wendi Xia; Junyi Ma; Jiaqi Zhang; Yiling Li (Human Genetics, 2026)

Whole-genome and Comparative Genomic Analysis Reveal the Biocontrol and Plant Growth-Promoting Potential of Bacillus velezensis JN.Y2 Against Oat Anthracnose - Wei Quan; Ting Zhang; Chen-Lu Liu; Shao-xuan Shi; Xi-xi Zhang; Ke-han Liu; Chun-Yang Wang; Ming-min Zhao; Bao-Zhu Dong; Hong-You Zhou (Functional & Integrative Genomics, 2026)

DBF4B promotes hepatocellular carcinoma progression by regulating CCNA2 and PSMD11 expression - Bing Dong; Pengju Xi; Guangxin Yang; Zhiqi Jiao; Shijie Xu; Lin Han; Zhenming Gao (Molecular Biology Reports, 2026)

Mechanism of water and nutrient competition between shelterbelts and farmland under different irrigation patterns in the Hexi Corridor oasis area, China - Yulian Hao; Haiyang Xi; Wenju Cheng; Tengfei Yu; Baofeng Li; Tuo Han; Yuqing Chen; Linbo Qu; Zhehui Wang (Soil and Tillage Research, 2026)

Sulfur cycling and its paleoenvironmental implications during OAE2: Evidence from the Qiangdong section, southern Tibet - Huifang Guo; Xi Chen; Hanwei Yao; Kaibo Han; Shujuan Wu; Jun Hu; Chengshan Wang (Global and Planetary Change, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Immunomodulatory effects of three herbal extract formulations on bovine peripheral blood mononuclear cells - Xi-Rui Xiang; Eun-Seo Lee; Jun Ho Lee; Su Min Kyung; Han Sang Yoo (Veterinary Immunology and Immunopathology, 2026)

Facilitating the commercialization of germinated foods: Integrated process and optimization for whole grain germination - Minyue Sun; Qianqian Yu; Wanda Xu; Yajuan Wang; Yanqin Zhao; Xiaobo Xi; Anqi Li; Yanlong Han; Xiangyi Meng; Yawen Xiao (Trends in Food Science & Technology, 2026)

Acoustic scattering characteristics of amplitude-induced wake-mode transitions in an oscillating-cylinder wake - Songhai Li; Dongbao Gao; Gensu Jia; Xi Han; Pengju He; Kaifeng Han (Ocean Engineering, 2026)

Rare earth element profiles and fractionation patterns in modern human dental enamel from Beijing, China - Lisheng Zhao; Xiaoyu Hu; Guilin Han; Di Wang; Wenqian Sun; Xi Gao (Journal of Trace Elements in Medicine and Biology, 2026)

A machine-learning-enhanced fuzzy evaluation framework for hydrochemical evolution and ecohydrological attribution in a megacity river basin - Jie Ren; Guilin Han; Xi Gao; Shitong Zhang; Qian Zhang (Journal of Hydrology, 2026)

Linking depositional environment with Pb-Zn-Ba mineralization during the Devonian transgression in South China: Insights from the Panlong deposit, Guizhong basin - Peng-Peng Yu; Jie-Jun Lei; Min Luo; Yi-Han Wu; Yi Zheng; Xi Chen; Hong-Xiang Shan; Lan-Xuan Guo; Bing-Bing Liao (Journal of Geochemical Exploration, 2026)

An explainable machine learning and PMF framework with SHAP-informed source prioritization for tracing water quality degradation in a large river basin - Xingnian Ren; Ailian Li; Xiufeng Shi; Shanshan Guo; Weishan Hu; Wanping Zhang; Xi Weng; Mingkun Guo; Qingsong Chen; Dongdong Gao; Han Zhang (Journal of Environmental Chemical Engineering, 2026)

In-situ generation of appropriate mixed-valence tin oxides on carbon nanofibers tuning CO2 reduction to formate - Wei Han; Xian Yue; Lu Liu; Fuzhi Li; Xianbo Yu; Hu Chen; Xiaoxue Xi; Shuao Xie; Zhongbo Hu; Huaxin Li; Junhui Xiang (Journal of Environmental Chemical Engineering, 2026)

Chemometrics and machine learning for efficient grading and sensory prediction of raw milk flavor - Yanmei Xi; Xuelu Chi; Lunaike Zhao; Weizhe Wang; Jianfeng Wang; Jiyu Han; Yufang Su; Baoguo Sun; Nasi Ai (Food Research International, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Rosa roxburghii-derived Mg-doped carbon dots as bioactive nanoregulators in hydrogel scaffolds: orchestrating Nrf2/NF-κB signaling for enhanced periodontal repair in diabetes - Xuedong Deng; Lingxiang Sun; Xi Chen; Zheng Wang; Yilin Ping; Wen Ze Han; Lu Wang; Tingting Wu; Yifan Zhao; Bing Li; Xiuping Wu (Chemical Engineering Journal, 2026)

High-performance sandwiched pressure sensors enabled by the synergism of multilayer assembly of hierarchical microstructures and interlayer conductivity mismatching - Xue Han; Xi Wang; Huijiang Li; Xiaotian Song; Jinsong Wang; Kaichen Zhang; Lirong Fan; Juanjuan Wang; Xiaopeng Li; Enping Liu; Xiaoli Zhang; Bin Wang; et al. (Chemical Engineering Journal, 2026)

Metal-node coupling of triboelectricity in conductive metal–organic frameworks for contact-electro-catalytic H2O2 generation - Meichen Li; Shuqi Zhou; Yinben Guo; Xueshuang Xiao; Qiqing Xi; Ximing Wang; Xin Han; Qiang Yang (Chemical Engineering Journal, 2026)

Agricultural management shapes soil multitrophic communities and biodiversity-ecosystem function relationships in a dryland agroecosystem - Jiayao Han; Yali Zhang; Hao Xi; Lin Mao; Zhou Fang; Chenyu Li; Yongjun Liu (Agriculture, Ecosystems & Environment, 2026)

Research on an automatic steering control strategy for unmanned tractors based on IDDPG-PID algorithm - Yangjie Shi; Chuanlong Chen; Wenjie Gao; Yu Wang; Lianjie Han; Xiaobo Xi; Wenkai Zhang; Hui Shen; Ruihong Zhang (Computers and Electronics in Agriculture, 2026)

Parameter optimization and experimentation of a dual mechanical disturbance weeding device for paddy fields - Yangjie Shi; Jintao Xu; Jiawang Hong; Lianjie Han; Xiaobo Xi; Zhengbo Zhu; Hui Shen; Ruihong Zhang (Crop Protection, 2026)

Genomic analysis of an Arctic marine Tenacibaculum sp. SM2510 reveals its genetic potential for glutathione utilization - Can You; Han Wang; Jing-Li Lv; Chang Tan; Xi-Ying Zhang; Hai-Yan Cao (Marine Genomics, 2026)

Erratum to “Genome-wide identification of StMAPKKKs and functional characterization of StMAPKKK44 in regulating salt and drought tolerance in potato (Solanum tuberosum L.)” [J. Plant Physiol. 323 (2026) 154799] - Xi Zhu; Kaitong Wang; Xiaoqin Duan; Xidan Pang; Xuanrong Du; Zhilin Han; Wei Li; Shu Chen; Hui Jin; Zhuo Chen; Yu Zhang; Yasir Majeed (Journal of Plant Physiology, 2026)

Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Numerical investigation on the influence of interstage leakage in a high-speed low-flow two-stage centrifugal refrigeration compressor - Yafei Duan; Dan Liu; Han Chen; Guang Xi (International Journal of Refrigeration, 2026)

Benchmarking backbone neural networks for HVAC fault diagnosis and regression: Insights into spatiotemporal, graph, and attention-based architectures - Zhe Sun; Peng Yang; Ling Shi; Qiwei Yao; Lin Li; Han Xiao; Xiangwei Zheng; Xi Shen (Energy and Buildings, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Dual-responsive hydrogel coils with shape memory effect for enhanced aneurysm embolization - Min Ye; Ming Qiu; Yunpeng Cai; Nanxiang Li; Jianguo Han; Yan Zhou; Yue Xi; Hongyu Zhao; Yujie Liao; Xinpeng Niu; Long Han; Qingsong Xu; et al. (Chemical Engineering Journal, 2026)

Isotope-aided frozen soil hydrological modeling reveals freeze–thaw controls on runoff partitioning in a mountainous catchment of the upper Heihe River, China - Leilei Yong; Yahui Wang; Qiaojuan Xi; Zehua Chang; Chuntan Han; Rensheng Chen; Hongkai Gao (CATENA, 2026)

Analysis of Culturable Endophytic Fungal Composition and Antioxidant Capacity Isolated From Eriocaulon nudicuspe Collected From the Tokai Hilly Land Spring‐Fed Mires - Wei Jiang; Weiwanqi Zhang; Qiong Han; Guang‐Xi Wang (New Zealand Journal of Botany, 2026)
This study focuses on Eriocaulon nudicuspe , an endangered herbaceous plant endemic to Japan, aiming to analyze the composition of its endophytic fungi and evaluate the antioxidant capacity of fungal isolates. E. nudicuspe samples were collected from three Japanese marshes: Yanami, Kamitaka, and Onshinji. Fungi were isolated using the tissue block method and identified based on morphological and molecular characteristics. The free radical scavenging activity of fungal organic extracts was assessed using the DPPH assay. A total of 69 fungal strains isolated from E. nudicuspe across the three wetlands were identified into 13 genera, among the three marshes, Yanami and Kamitaka Marsh each harbored 9 genera, whereas Onshinji Marsh harbored only 3. The dominant genus was Colletotrichum , which accounted for 39.13% of all isolates from leaves and stems, followed by Stagonospora . Notably, Colletotrichum was significantly more abundant in leaves than in stems, suggesting a strong tissue preference. In contrast, Stagonospora was more prevalent in stems. DPPH radical‐scavenging rates also varied significantly among marshes, with isolates from Yanami Marsh showing higher antioxidant activity, both in average and maximum values. The abundance of Colletotrichum was strongly associated with leaf tissues, while variations in fungal community structure across sample regions suggest that geographical location influences endophytic composition.

Stability Analysis of Multi-Stage Bench Slopes based on Frequency Characteristics - Peng Yan; Xi Yang; Han Wang; Ziheng Jia; Zhiyi Liu; Yunpeng Zhang; Deqing Gan (Rock Mechanics and Rock Engineering, 2026)

THBS2: the key hub linking breast cancer stroma, immunity, and therapeutic response - Xi Wan; Xinchen Zhao; Yao Lin; Shujie Yang; Han Dai; Yi Li; Xiaoshan Wang (Clinical & Experimental Metastasis, 2026)

A Neuroimaging Biomarker for Hippocampal Network Dysfunction in Alzheimer’s Disease - Jiangping Wu; Pan Wang; Dawei Wang; Hongxiang Yao; Bo Zhou; Jie Lu; Xi Zhang; Ying Han; Yonghua Zhao; Yihe Zhang; Kun Zhao; Yong Liu (Neuroscience Bulletin, 2026)

Design and evaluation of an active shielded capacitive sensor system for real-time wheat seed mass-flow monitoring - Lianjie Han; Yu Wang; Yunhan Zou; Jieyuan Ding; Yangjie Shi; Ruihong Zhang; Xiaobo Xi (Computers and Electronics in Agriculture, 2026)

Making waves: Harnessing the disinfection byproduct chlorite as an oxidant precursor for micropollutant abatement - Xi Zhang; Yimeng Ma; Mingkai Jia; Wanxin Li; Jiarui Han; Rihui Li; Xin Yang; Ran Yin; Hongqiang Ren (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Efficient discovery of eight unreported compounds in Tall Gastrodia Tuber (Tianma) by stratified-precursor-list-based molecular network analysis and LC-MS-guided isolation - Han Yu; Tianren Wu; Zhaohui Li; Xi Mao; Chunfeng Li; Caihong Bai; Meng Qiang; Shiwei Huang; Kaifeng Hu; Guanghua Lu (Phytochemistry, 2026)

Predefined-time global prescribed performance tracking of ASV via adaptive event-triggered control - Peng Chen; Tao Han; Bo Xiao; Yuan Tan; Xi-Sheng Zhan; Ming-Feng Ge (Ocean Engineering, 2026)

Genome-wide identification of StMAPKKKs and functional characterization of StMAPKKK44 in regulating salt and drought tolerance in potato (Solanum tuberosum L.) - Xi Zhu; Kaitong Wang; Xiaoqin Duan; Xidan Pang; Xuanrong Du; Zhilin Han; Wei Li; Shu Chen; Hui Jin; Zhuo Chen; Yu Zhang; Yasir Majeed (Journal of Plant Physiology, 2026)

Indium enrichment in VMS deposits: insights from sphalerite geochemistry and thermodynamic modeling of the Tiemurt Pb-Zn-Cu deposit, NW China - Min Luo; Peng-Peng Yu; Yi Zheng; Jie-Jun Lei; Xi Chen; Yi-Han Wu; Hong-Xiang Shan; Quan-Jie Li; Zhuo-Xiong Shi (Journal of Geochemical Exploration, 2026)

From Waste to Efficient Energy: Multidimensional Additive-Mediated Regulation of Aged Garbage-Based Refuse Derived Fuel (RDF) Performance - Donglin Han; Nannan Li; Sunxin Xia; Yu Xi; Xiaomao Song; Meijuan Kuang; Lei Yang; Tianpeng Zhou; Xiang Liang; Guohao Li; Yu Shi; Zhihua Xu (Fuel, 2026)

Corrigendum to “Sodium cyclamate enhances Vibrio parahaemolyticus biofilm formation on seafood-contact surfaces” [Food Res. Int. 235 (2026) 119195] - Yining Zhou; Nan Zhang; Wu Xu; Xue Li; Miaomiao Zhang; Xi Luo; Bin Ni; Feng Huang; Renfei Lu; Yiquan Zhang; Xudong Han (Food Research International, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Effects of mesoscale eddies on near-bottom dynamics in the continental slope of northern South China Sea - Hao Chen; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Xiao-Dong Shang; Jia-Jing Chen; Ze-Yao Weng; Wen-Dong Fang; Yuan-Zheng Lu; Guang-Hui Han (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

A bionic superhydrophobic strain sensor for underwater motion monitoring and hazard warning - Hanpeng Gao; Yujie Lv; Xi Wang; Zong Meng; Zhiwu Han; Yan Liu (Chemical Engineering Journal, 2026)

From seasonal variation to grazing management: Aerodynamic and radiative controls on air heat and moisture distribution in grasslands - Ruishen Li; Shengwei Zhang; Guodong Han; Xi Lin; Meng Luo; Shuai Wang; Zhimou Cui (CATENA, 2026)

Modern human dental enamel as a biomineral baseline for rare earth elements and yttrium in urban Nanjing, China - Xiaoyu Hu; Lisheng Zhao; Ziyang Ding; Xi Gao; Di Wang; Wenqian Sun; Biao Zhu; Guilin Han (Environmental Geochemistry and Health, 2026)

A Mid-Pleistocene Provenance Shift in the Bohai Strait at 0.94 Myr: Implications for Synergistic Controls on Yellow River Integration - Wei Xiong; Xi Mei; Long Huang; Naishuang Bi; Zongzhu Han; Yong Zhang; Zhonglei Wang (Journal of Ocean University of China, 2026)

Salvianolic acid B suppresses non-small cell lung cancer growth by promoting Nrf2 proteasomal degradation and triggering autophagy-dependent ferroptosis - Kejing Xi; Han Xiao; Zixin Yin; Linfang Jin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Engineering phage endolysins and receptor-binding proteins for foodborne pathogen control and detection: A review and AI-driven framework - Zongcheng Wu; Xiaofeng Yu; Honglin Ren; Chunyi Shangguan; Cheng Han; Xi Yang; Shuaihao Qi; Xuepeng Duan; Han Wang; Pan Hu; Yansong Li; Qiang Lu; et al. (International Journal of Food Microbiology, 2026)

Sodium cyclamate enhances Vibrio parahaemolyticus biofilm formation on seafood-contact surfaces - Yining Zhou; Nan Zhang; Wu Xu; Xue Li; Miaomiao Zhang; Xi Luo; Bin Ni; Feng Huang; Renfei Lu; Yiquan Zhang; Xudong Han (Food Research International, 2026)

Decoding health burdens of ground-level ozone exposure in megacities through a 5-year spatiotemporal analysis of Shenzhen, China - Han Wang; Jiayi Fu; Hao Huang; Junmao Zhang; Xi Tan; Honggang Ni; Jiansheng Wu (Environmental Impact Assessment Review, 2026)

Triple-synergy Strategy for High-phosphorus-retention High-temperature Proton Exchange Membranes at 40–160 °C for Fuel Cell - Linjian Sang; Qian Wang; Panlong Zhou; Heguo Han; Jianhang Qiu; Xi Sun; Hang Zhang; Guorui Qin; Jifu Zheng; Shenghai Li; Suobo Zhang (Chemical Engineering Journal, 2026)

Abundance, characterization, and distribution of atmospheric microplastics in three major cities in China - Xi Li; Yuantong Zhu; Jingzhi Wang; Han Song; Laiguo Chen; Donghao Wang; Ruiyuan Wang; Zhibao Dong; Yongming Han; Junji Cao (Atmospheric Pollution Research, 2026)

Dynamic response and failure evolution of sandy slopes under ground motion before and after rainfall infiltration - Junyan Han; Jiasai Li; Xi Xu; M. Hesham El Naggar; Zhaohui Wang; Chengshun Xu; Xiuli Du (Landslides, 2026)

Diverse impact of the western North Pacific sea surface temperature anomalies on El Niño–Southern Oscillation among CMIP6 models: dependence on the background meridional sea surface temperature gradient - Zhouji Wang; Yuqiong Zheng; Linye Song; Feng Han; Zhibiao Wang; Xi Cao; Wen Chen; Shangfeng Chen (Climate Dynamics, 2026)

Chitin Synthase Is Critical for Epidermal Chitin Deposition and Molting in the Swimming Crab Portunus trituberculatus - Yaoyao Han; Xi Xie; Dongfa Zhu (Fishes, 2026)
Chitin synthase (CHS) catalyzes the final polymerization step in chitin biosynthesis and is therefore central to cuticle formation in arthropods. In this study, a chitin synthase gene from the swimming crab Portunus trituberculatus (PtCHS) was identified and functionally characterized in relation to epidermal formation and molting. The open reading frame of PtCHS was 4731 bp and encoded a predicted protein of 1576 amino acids belonging to glycosyltransferase family 2. Domain prediction revealed multiple transmembrane helices, a conserved chitin-synthase catalytic region, a coiled-coil region, and the diagnostic EDR, QRRRW, and SWGTRE motifs. Phylogenetic analysis assigned PtCHS to the class A/CHS1 chitin synthase lineage, and two alternative splice variants, designated PtCHS1a and PtCHS1b were detected. PtCHS transcripts were broadly distributed across examined tissues, with comparatively high abundance in the Y-organ, midgut, ovary, and epidermis. During the molting cycle, epidermal PtCHS expression increased during premolt, reached its highest level in postmolt stages, and declined during intermolt. During embryonic development, PtCHS expression remained relatively stable until late embryogenesis and then increased sharply before hatching. RNA interference-mediated knockdown of PtCHS reduced the expression of key chitin-biosynthesis genes, decreased epidermal chitin content, prolonged the molting interval, and was associated with molting failure and increased mortality. Conversely, unilateral eyestalk ablation induced PtCHS and molting-related genes, increased epidermal chitin content, shortened the molting interval, and promoted histological features consistent with enhanced extracellular matrix deposition and epidermal biosynthesis. These findings indicate that PtCHS is indispensable for epidermal chitin deposition and successful molting in P. trituberculatus, and provide a molecular basis for understanding molting regulation in economically important portunid crabs.

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Communication capability evaluation method for ad hoc networking scenarios on marine vessels - Yu Zhu; Yongtao Xi; Bin Han; Zhongdai Wu (Ocean Engineering, 2026)

Experimental investigation of nonlinear hydrodynamic properties of the T-foil on a high-speed trimaran - Shijie Liu; Lincen Han; Hongyu Lin; Shaoqing Liu; Xi Chen; Yichen Jiang (Ocean Engineering, 2026)

Coupling health risk constraints and source apportionment to quantify environmental capacity consumption of soil heavy metal(loid)s in urban green spaces — A case study in Shanghai, China - Zhancheng Wang; Quanbo Yu; Huijuan Wang; Yangyang Hu; Zhen Wei; Xiaohui Luo; Tingting Xu; Rongxi Li; Zilin Han; Jiaheng Wu; Xi Zhang; Qicheng Zhong; et al. (Journal of Hazardous Materials, 2026)

Based on the “biotin-streptavidin” system to construct exosome- linked hydrogel for promoting healing of chronic wounds in obesity by regulating the NF-κB pathway - Lingxiang Sun; Wenze Han; Yilin Ping; Xi Chen; Xuedong Deng; Zheng Wang; Jingjing Deng; Jian Zhou; Tingting Wu; Yifan Zhao; Xiuping Wu; Bing Li (Chemical Engineering Journal, 2026)

Corrigendum to “Modification of starch traits in commercial wheat through TaWaxy gene editing” [Carbohydrate Polymers 368 (2025): 124105] - Yuliang Qiu; Xi Li; Ming Fan; Huali Tang; Shuangxi Zhang; Weihong Huang; Zhiyang Han; Surong Wang; Hao Peng; Yonggui Xiao; Xingguo Ye; Ke Wang (Carbohydrate Polymers, 2026)

Mosquito-borne disease among individuals experiencing homelessness in the USA: a literature review - André B. B. Wilke; Megan D. Hill; Allisandra G. Kummer; Chalmers Vasquez; John-Paul Mutebi; Xi Huo; Han Li; Jing Chen; Shigui Ruan; John C. Beier; Maria Litvinova; Thomas Byrne; et al. (Journal of Pest Science, 2026)
Mosquito-borne diseases are a major public health issue. The USA has experienced mosquito-borne disease outbreaks, including West Nile virus, Zika, dengue, and malaria, highlighting widespread risk across the country. In the USA, exposure to mosquito vectors primarily occurs outdoors. Individuals experiencing unsheltered homelessness are particularly vulnerable to mosquito-borne diseases due to their increased exposure to mosquito vectors, limited access to healthcare, and high prevalence of underlying conditions. This review aims to examine the literature on mosquito-borne disease infections among individuals experiencing homelessness in the USA between 1999 and 2024. Our search strategy used Boolean methods on PubMed, Scopus, and Web of Science to select relevant publications. Two queries were used: the first query focused on individuals experiencing homelessness and mosquito-borne diseases, and the second one focused on epidemiological analyses of mosquito-borne disease outbreaks in the USA. Only studies reporting at least one infection among individuals experiencing homelessness were included. Our search resulted in the identification of 347 studies. After screening them, eight were ultimately included in this review. Half of the studies identified West Nile virus among individuals experiencing homelessness, and the other half reported cases of malaria. These studies show that individuals who spend more time outdoors, including individuals experiencing homelessness, may be at a greater risk of MBDs compared to the general population. However, the full extent of mosquito-borne disease exposure among individuals experiencing homelessness remains unclear. With climate change and globalization, there is a consensus in the literature showing an increasing risk of mosquito-borne disease transmission in the next decades, and we have already started to witness this increasing trend. Moreover, the USA is experiencing a steep increase in the overall nationwide homeless population. Therefore, we argue that developing policies aimed at providing homeless populations with housing during mosquito-borne disease outbreaks could be instrumental in protecting this segment of the population and promoting health equity.

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Succession and Functional Adaptation of Bacterial and Fungal Communities in Biological Soil Crusts Responding to Uranium Stress - Mengwei Han; Hua Zhao; Jinlong Lai; Sanping Zhao; Bin Dong; Hailing Xi (Environmental Microbiology, 2026)
Uranium (U) mining causes severe radioactive contamination threatening ecosystems. Biological soil crusts (BSCs), as pioneer communities in degraded habitats, show strong heavy metal accumulation potential, yet their adaptive mechanisms under U stress remain unclear. In this study, BSCs from a uranium tailings dam in Hunan Province were exposed to simulated U stress. Results showed that BSCs exhibited exceptionally high U accumulation capacity (up to 4131 mg/kg), and effectively immobilised U by converting it into residual and organic‐bound fractions (collectively > 70%) via carboxyl complexation and microbial mineralisation, thus significantly reducing environmental mobility. U stress caused damage to the photosynthetic and antioxidant systems of the BSCs. Microbial community complexity decreased, with tolerant taxa including Proteobacteria and Bacilli significantly enriched. Metagenomics revealed distinct cross‐kingdom functional adaptation strategies: bacteria upregulated energy metabolism and acetaldehyde metabolism to facilitate efflux detoxification, while fungi strengthened lipid homeostasis and antioxidant metabolism. Several U‐tolerant strains ( Bacillus, Aspergillus and Penicillium ) closely associated with U immobilisation were further isolated and verified. This study systematically reveals the synergistic tolerance mechanisms of BSCs under U stress and provides key microbial resources and theoretical support for the in situ bioremediation of U‐contaminated sites.

Source identification and coastal export of sulfate in a megacity river: Insights from sulfur isotopes and inverse model - Xuehui Liu; Guilin Han; Jinke Liu; Jie Ren; Xi Gao; Di Wang (Marine Pollution Bulletin, 2026)

Experimental investigation on the fire performance of novel multi-scale fiber reinforced UHPC segments - Yao Zhang; Ruanxiang Xiong; Panpan Cheng; Yibo Chen; Weigang Zhao; Kaihang Han; Xi Jiang; Hehua Zhu; Zhiguo Yan (Tunnelling and Underground Space Technology, 2026)

A port state control data-driven predictive maintenance framework for MASS using hybrid complex neural networks - Mengqin Li; Yongtao Xi; Cunlong Fan; Bing Han; JiaXin Du; Yan Chen (Ocean Engineering, 2026)

Emission characteristics and health risk assessment of oil mist and VOCs in several typical industrial processes - DingChao Zhang; Yuying Li; Xin Wang; Kehao Qin; Mengfei Han; Xi Chen; Ziyuan Li; Xin Zhang; Yanling Guan (Journal of Hazardous Materials, 2026)

Embedding Bi sandwich structure Bi2O3/Bi/TiO2 photocatalyst for enhancing the durable degradation of toluene - Liuhan Guo; Hehua Liao; Shitong Han; Dongmiao Li; Bing Wang; Jinni Shen; Wenxin Dai; Xuxu Wang; Zizhong Zhang; Hailing Xi (Journal of Environmental Sciences, 2026)

Responses of grassland ecosystem temporal stability to biotic and abiotic drivers in arid and semi-arid regions of China - Yunxiang Han; Huayong Zhang; Bingjian Zhao; Xi Luo; Xiao Zhang (Journal of Arid Environments, 2026)

Synergistic construction of OSA-ferulic acid composite starch: Structural evolution, gel properties, and its regulation on lamb meat flavor - Meijuan Xu; Pei Yan; Xinfeng Yue; Yating Han; Xi Han; Linping Yao; Xiaojing Ma; Yuanbo Xiao; Dequan Wei; Jian Zou (Food Research International, 2026)

Substrate-dependent modulation of microbial assembly and flavor metabolism by medicine food homology (MFH) additives in high-temperature Daqu - Haideng Li; Jianing Liu; Ying Lang; Xi Chen; Xucheng Zhu; Xinyi Zhang; Hexu Han; Weiwei Li; Xiuting Li; Baoguo Sun (Food Bioscience, 2026)

Multiscale damage mechanisms of limestone under acid, alkali, and cyclic conditions - Han Zihao; Meldi Suhatril; Huzaifa Hashim; Puteri Azura Sari; Zhu Xi (Bulletin of Engineering Geology and the Environment, 2026)
Chemical corrosion is a critical factor driving the degradation of rock engineering properties, particularly in carbonate-rich formations. To investigate the mechanisms of limestone deterioration under extreme chemical conditions, this study conducted continuous immersion tests in acidic (pH = 2, H₂SO₄) and alkaline (pH = 12, NaOH) solutions, together with wet–dry cycling and acid–alkali alternation experiments. A control group without chemical treatment was also included for comparison. The macroscopic and microscopic responses of limestone were systematically analyzed through porosity, mass loss, P-wave velocity, uniaxial compressive strength, and microstructural characterization. Results revealed that degradation severity followed the order: acid–alkali alternation > acidic wet–dry cycling > continuous acid immersion > alkaline ≈ control. After 30 days, the acid–alkali alternation group exhibited the most severe deterioration, with porosity increasing from 0.29% to 0.42%, mass loss reaching 0.92%, P-wave velocity decreasing from 5796 m/s (10 days) to 5268 m/s (30 days), and UCS declining from 43.83 MPa (10 days) to 33.73 MPa (30 days). At the microscale, acidic conditions promoted CaCO 3 dissolution with CaSO₄ precipitation (up to 11.6% during wet–dry cycles), enlarging pores and pore throats, while acid–alkali alternation triggered cyclic precipitation–dissolution stresses that produced interconnected microcrack networks. In contrast, alkaline conditions showed only weak passivation and precipitation. A strength prediction model was established based on the chemical damage variable D defined by P-wave velocity, which exhibited a strong power-law relationship with strength (R 2 ≈ 0.93). This study explains three coupled mechanisms—dissolution-dominated, dissolution–crystallization synergy, and chemical fatigue—and proposes a simple, economical, and non-destructive velocity–strength framework for rapid durability assessment and early warning in acid rain, industrial effluent, and underground engineering contexts.

Colletotrichum aenigma causes anthracnose disease of Ficus carica L. in China - Yu-kun Qi; Wen-zhang Liu; Feng-ying Han; Wen-cheng Zhu; Shi-jun Sun; Qing-hai Wang; Ling-xi Zhou (Crop Protection, 2026)

Per-and poly-fluoroalkyl substances in lung tissues and their association with lung cancer - Xi-Ze Min; Li Ma; Fei Chen; Ying-Hua Hu; Chao Jiang; Yi-Fan Li; Yue Han; Zi-Feng Zhang; Kurunthachalam Kannan (Journal of Hazardous Materials, 2026)

Effects of plasma excitation parameter gradients on alfalfa physiological traits under salt stress - Junhui Xi; Yunting Hui; Shouyan Wang; Jinlong Liu; Decheng Wang; Yong You; Qian Han; Kun Ji; Xiaoyi Zhou; Yangyang Liao; Sibiao Li (Journal of Cleaner Production, 2026)

A novel process for extracting tungsten from photovoltaic tungsten-based busbars scrap based on molten salt electrolysis - Xiang Xue; Liwen Zhang; Qi Fang; Chunjia Liu; Shuijie Su; Han Zhang; Junming Ma; Xiaoli Xi; Zuoren Nie (Journal of Environmental Management, 2026)

Electro-Fenton treatment of complex PCB (Printed Circuit Board) wastewater: Dominant reactive species, chloride-mediated nitrogen removal - Dengxiang Fan; Yunlong Dong; Lequn Sun; Jingtao Sun; Han Zhang; Miaomiao Yang; Weiwei Xi; Liu Jiang; Rongfang Yuan; Beihai Zhou; Huilun Chen; Shuai Luo (Journal of Environmental Chemical Engineering, 2026)

Water quality assessment in a megacity river: Water chemical analysis integrated with AHP-Entropy weighted fuzzy comprehensive evaluation model - Jie Ren; Guilin Han; Xi Gao; Shitong Zhang (Journal of Environmental Sciences, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

An explainable machine learning approach (SHAP) to assessing desertification risk and its drivers in the Ring-Tarim Basin, 1990–2020 - Lei Xi; Zhao Qi; Yiming Feng; Xiaoming Cao; Jiaxiu Zou; Jie Han (Environmental Impact Assessment Review, 2026)

Precision pore engineering of platinum group metal-free catalysts for high performance anion-exchange membrane fuel cells - Chaoqi Han; Hao Liu; Jie Yang; Wenwen Shi; Qi Wang; Ruimin Ding; Xi Yin (Chemical Engineering Journal, 2026)

The characteristics of the atmospheric boundary layer structure over the Cosmonaut Sea and Bellinsgauzen Sea during summer 2021 - Ting Qiu; Qinghua Yang; Bo Han; Xingya Xi; Zhongya Cai; Shijie Peng; Changwei Liu (Atmospheric Research, 2026)

Holistic overview of regulatory networks governing seed dormancy and germination in plants - Kunrong He; Weimin Wang; Chengxiang You; Xianting Qi; Xi Chen; Xu Wang; Milian Yang; Minghui Zhang; Ruyu Tang; Zhichong Huang; Juping Zhang; Jingwen Ye; et al. (Science China Life Sciences, 2026)
Seed dormancy and germination are crucial processes affecting the propagation and survival of plant populations. These phenomena are precisely regulated through a complex interplay between internal signals, such as plant hormones and environmental cues including light, temperature, moisture, and nutrient availability. Dormancy release and germination initiation are distinct, yet closely associated, processes involving complex transcriptional, translational, and epigenetic changes mediated by intricate regulatory mechanisms. This review comprehensively summarizes the complex regulatory networks governing seed dormancy and germination across different plant species. By integrating physiological, genetic, and molecular biology perspectives, the latest advances in the research on mechanisms regulating seed dormancy and germination are discussed, providing valuable insights for improving seed quality through biotechnology-based breeding strategies and establishing a solid foundation for future research in this field.

P2X7 receptor-mediated cGAS-STING pathway activation underlies chronic stress-induced depressive-like behaviors - Xi-Meng He; Yi Zhang; Cui-Yuan Chen; Yu-Li Han Tang; Xuan Li (Purinergic Signalling, 2026)

Nanozyme fabrication based on magnetic COFs and gold nanorods and its SERS detection of zearalenone - Xiaoyuan Ma; Xi Ma; Muxi Zhang; Jinchi Han; Zhouping Wang (Analytica Chimica Acta, 2026)

Global-to-regional variations in the effects of grassland management on soil carbon - Xi Lin; Shengwei Zhang; Alfredo Huete; Han Y.H. Chen; Hongbin Zhao; Qinsi He; Shengwei Lv; Qian Zhang; Xiaoduo Zhang; Xiaofeng Zhang (Agriculture, Ecosystems & Environment, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Decode the Ubiquitinome in Parkinson’s Disease: From Pathological Aggregates to Targeted DUB Therapeutics - Xi Yu; Qinshuai Ni; Litong Han; Shenghan Zhang; Huamin Xu; Junxia Xie; Yingjuan Liu (Neuroscience Bulletin, 2026)

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

Biological activity of alkaloids from kenaf bast fibres - Xiangyuan Feng; Lifeng Cheng; Guoguo Xi; Ke Zheng; Zhenghong Peng; Fengbo Han; Qi Yang; Shengwen Duan (Natural Product Research, 2026)

Statistical Characteristics and Spatial Distributions of Aerodynamic Loads on Offshore Fixed-Bottom Wind Turbines under Wake Interference - Yan-zhong Ren; Ming-xi Liu; Hao Lu; Xiao-xia Gao; Zhe Wu; Lei Zhang; Zhong-he Han (Applied Geophysics, 2026)

Source apportionment and probabilistic risks of potentially hazardous metals in a typical agricultural river basin, Thailand: Implications for sustainable sediment remediation - Xi Gao; Guilin Han; Shitong Zhang; Shunrong Ma (Process Safety and Environmental Protection, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Mechanistic insights into magnetite-enhanced Indoleacetic acid production by a mixed culture - Yun-Xin Ge; Wei Gao; Zi-Han Fan; Yun Niu; Long-Tao Fang; Xi-Zhen Zou; Wei Zhang (Journal of Water Process Engineering, 2026)

Towards efficient chemical reduction of perchlorate in water: Mechanisms, design considerations, and future directions - Yiran Feng; Xi Chen; Zhenmin Zhang; Han Yang; Yabo Liu; Lei Dong; Lingjun Bu; Shiqing Zhou; Hejie Qin; Xiaohong Guan (Journal of Hazardous Materials, 2026)

Microbial regulation of phosphorus cycling under soil amendments and shrub selection in arid limestone mine restoration - Mingzhu He; Yuanshang Guo; Huijun Qin; Jing Zhou; Chunming Xin; Shengzhong Du; Xi Zhang; Wenjin Wu; Guojun Han (Journal of Environmental Management, 2026)

Influence of peel morphology on pesticide distribution and metabolic responses in mango after postharvest immersion treatment - Xuan Zhu; Rui Zhang; Xi Liao; Shuhuai Li; Bei Li; Bing Qian; Tietao Zhang; Bingjun Han (Food Research International, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Multi-strategy rehabilitation enhances nitrogen removal in a one-stage partial nitritation/anammox reactor - Xinyu Wan; Zhicheng Zhao; Yunpeng Zhao; Wan Sun; Shilong Liu; Xiangyu Han; Xi Lu; Yasong Chen; Weiwei Cai (Environmental Research, 2026)

Material innovations and defect-driven mechanisms in capacitive deionization for efficient fluoride removal - Jingtao Sun; Yunlong Dong; Lequn Sun; Dengxiang Fan; Han Zhang; Miaomiao Yang; Weiwei Xi; Liu Jiang; Rongfang Yuan; Beihai Zhou; Huilun Chen; Shuai Luo (Desalination, 2026)

Engineering hierarchical pores in FeCo-N-C catalysts to construct advanced cathode catalyst layers for AEMFCs with alleviated water management - Chaoqi Han; Ming Chen; Wenwen Shi; Ruimin Ding; Junliang Zhang; Xi Yin (Chemical Engineering Journal, 2026)

Highly effective multifunctional modifiers for all inorganic HTL-free carbon-based CsPbBr₃ perovskite solar cells - Chang Xu; Yinuo Liu; Xi Wang; Chang Zhao; Xuan Li; Jianing Guo; Qianji Han; Mingxing Wu (Chemical Engineering Journal, 2026)

Empowered rechargeable solid-state Mg O2 battery using free-standing N-doped 3D nanoporous graphene - Zeyu Xi; Hua-Jun Qiu; Samuel Jeong; Jiuhui Han; Kailong Hu; Yoshikazu Ito (Chemical Engineering Journal, 2026)

Keratan sulfate revisited: UPLC–MS/MS-based quantitative profiling reveals structural heterogeneity and deficiency in ocular pathologies - Xinping Wang; Han Zhou; Xi Liang; Yue Li; Shimei Shen; Yuxin Li; Qingfeng Niu; Bi Ning Zhang; Shuying Xu; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2026)

Flash joule heating-induced synthesis of biowaste-derived metal-free catalysts for nitrate reduction reaction - Xin Chen; Zhaoyu Wang; Liuhong Yang; Runmiao Yuan; Shuyi Huang; Qinyuan Hu; Xue Wang; Cong Gu; Xiangli Wen; Xi Chen; Hongji Zhang; Dongjian Shi; et al. (Bioresource Technology, 2026)

Recycled biochar-based powdery reagent for degradation of organic chromium complex dye: preparation, evaluation and kinetic modeling - Yuanfeng Qi; Qi Gao; Feng Han; Fei Xi; Xueqing Shi; Yunfei Zhang; Jun Zhang (Bioresource Technology, 2026)

Divergent responses of soil organic and inorganic carbon to edaphic factors within shelterbelts and croplands in dryland, Northwest China - Tengfei Yu; Tuo Han; Yidan Yin; Baofeng Li; Haiyang Xi; Wei Liu; Qi Feng (Plant and Soil, 2026)

Potential Transmission of Alpha-Synuclein from the Gastrointestinal Tract to the Substantia Nigra along the Vagal Afferent Pathway - Fan Han; Meiqiu Liu; Qian Jiao; Xixun Du; Chunling Yan; Xi Chen; Hong Jiang (Neuroscience Bulletin, 2026)

Research on design and prediction model of tunnel safety micro-deformation radar monitoring system - Zi-heng Gao; Gu-hua Pu; Jin-zhuang Wang; Meng-wei Han; Qiang He; Xiao-long Wang; Jian-bo Yang; Xiao-yu Yin; Jia-gui Duan; Liang Bao; Xi-can Zhao; Wei-jian Liu (Applied Geophysics, 2026)

Tunnel Micro-deformation Monitoring Method Based on Improved PS-InSAR and Its Geophysical Application Analysis - Meng-wei Han; Gu-hua Pu; Jin-zhuang Wang; Zi-heng Gao; Xiao-qian Yang; Bo Zhang; Ba-he Yang; Jun Ma; Hai-yun Wang; Yong-can Chen; Xi-can Zhao; Wei-jian Liu (Applied Geophysics, 2026)

Tooth Enamel as a Biogeochemical Archive of Trace Elements in an Urban Population: A Multielement Study from Beijing, China - Xiaoyu Hu; Lisheng Zhao; Ziyang Ding; Xi Gao; Guilin Han (Biological Trace Element Research, 2026)

Analyzing the synergistic relationship of FWEE-SDGs in the inland river basins using bi-level fuzzy multi-objective optimization: a case study of the Aral Sea Basin - Chaoliang Chen; Zengyun Hu; Tie Liu; Xi Chen; Kurishbayev Akylbek Kazhigulovich; Duman Yimamaidi; Weifeng Guo; Yesong Han (Environment, Development and Sustainability, 2026)

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

A wood–electric-eel inspired biomimetic membrane with self-monitoring capability for efficient oily wastewater treatment - Hanpeng Gao; Zhihao Sun; Ana Sofia Oliveira Henriques Moita; Xi Wang; Zong Meng; Zhiwu Han; Yan Liu (Journal of Hazardous Materials, 2026)

Quantifying volcanism during Oceanic Anoxic Event 2 constrained by sedimentary mercury - Yi Zhang; Hanwei Yao; Yinggang Zhang; Paul R. Bown; Stephen E. Grasby; Runsheng Yin; Kaibo Han; Huifang Guo; Chengshan Wang; Xi Chen (Global and Planetary Change, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Phosphorus fates in algal-bacterial granular sludge systems under different nitrogen transformation pathways - Xinyu Lyu; Xi Zhao; Han Shao; Zhichen Li; Tian Yuan; Motoo Utsumi; Kazuya Shimizu; Zhongfang Lei (Chemical Engineering Journal, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Calcium and copper isotope compositions in hydrothermally influenced sediments as proxies for hydrothermal activity on mid-ocean ridges: An example from the Carlsberg Ridge - Jian-Qiang Wang; Shuang-Shuang Lyu; Zhong-Yan Qiu; Xi-Qiu Han; Mou Li; Chun-Feng Li; Xue-Gang Chen (Chemical Geology, 2026)

Discrimination of seismic event near the North Korean nuclear test site (January-March 2022) using multi-station P/S spectral ratios - Bo-Han Wang; Lian-Feng Zhao; Xiao-Bi Xie; Xi He; Yong Zhao; Zhen-Xing Yao (Journal of Seismology, 2026)

The Enhancement and Variation in the Carbon Dioxide Concentration in a Typical Industrial Park in the Northern China - Qixiang Cai; Zhaojun Wang; Pengfei Han; Ning Zeng; Xi Nie; Xiaoyu Yang; Zhenyang Wang; Sulian Gao (Aerosol Science and Engineering, 2026)

Reducing the Discrepancy in Quantifying the Temperature Dependence of Global Wetland Methane Emission - Han Hu; Ke Xue; Yishen Sun; Qing Zhu; Hans K. Carlson; Ruiwen Hu; Rong‐Xi Tan; Chao Qian; Weigen Huang; Jizhong Zhou; Jingdong Mao; Thomas W. Crowther; et al. (Global Change Biology, 2026)
Understanding the apparent temperature dependence of wetland methane emissions ( E M ) is critical for predicting climate‐carbon feedbacks, yet current estimates remain constrained by observational limitations and methodological inconsistencies. The inherent biogeographic heterogeneity of wetland ecosystems combined with sparse, unevenly distributed flux measurements introduces substantial uncertainty in characterizing spatial patterns of E M . This knowledge gap impedes accurate projections of wetland methane contributions under climate warming scenarios. Here, we develop a framework that integrates mixed‐effects models with artificial intelligence techniques to resolve scale‐dependent patterns in methane emission thermodynamics across global wetlands. Our unified framework demonstrates that only 73.6% (5th–95th quantiles: 71.8%–75.4%) of the global wetland area conforms to classical Arrhenius‐type temperature dependence. This framework can predict 69.5% (67.9%–71.1%) of the global wetlands with high confidence using the Mahalanobis distance and area of applicability tests. We quantify the weighted mean E M across high‐confidence predictable areas of 0.694 eV, with latitudinal differentiation: tropical (0.634 eV), temperate (0.678 eV), and boreal (0.745 eV) wetlands exhibit progressively stronger temperature responses. Ignoring these biogeographic variations could result in underestimation of projected end‐century methane emissions by 4.2%–13.3% across selected socioeconomic pathway scenarios. Our study refined the temperature sensitivity parameter in coupled climate‐carbon cycle models, thereby enhancing predictive accuracy of future global warming trends and informing strategic responses to climate change mitigation.

Expression of key genes in IVIG-unresponsive Kawasaki disease and their immune correlation based on bioinformatics analysis - Zheng-Han Zhao; Xi-Yu Yang; He Zhang; Shu-Jun Li; Yan Li (Immunologic Research, 2026)

Periodic coupling of anthropogenic fire patterns and East Asian monsoon variability over the past 4000 years - Hao Lei; Zhihai Tan; Yongming Han; Longjiang Mao; Penglong Yue; Chenhao Xi; Yubo Yuan; Chunhui Zou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to ‘Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems’ [J. Environ. Manag. 395 (2025) 128013] - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Analysis of triacylglycerol composition in giant panda (Ailuropoda melanoleuca) milk fats from different lactation stages - Xi Cao; Caoqi Jiang; Haojun Han; Dongjie Zuo; Guiquan Zhang; Yikun Xian (International Dairy Journal, 2026)

Synergistic microbial co-culture of Saccharomyces cerevisiae and Clostridium kluyveri enhances ethyl hexanoate production for stable flavor synthesis in strong-flavor Baijiu - Qiumei Zhang; Ru Zhang; Xi Chen; Meiyue Han; Ya Zhang; Weiwei Li; Xiuting Li; Jianxiong Hao; Baoguo Sun (Food Bioscience, 2026)

Effects of elevated atmospheric CO2 on hybrid rice (Oryza sativa L.) starch granules: Structural, functional changes and their underlying causes - Liquan Jing; Xi Gong; Yang Cai; Yu Su; Mohamed Ait-El-Mokhtar; Mingxing Lu; Zhuo wang; Lianxin Yang; Qing Han; Yunxia Wang (Carbohydrate Polymers, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

Targeting P2X7R Protects the Retina Against High-Altitude Hypoxia via NLRP3–Mediated Pyroptosis Suppression - Keke Ge; Yange Gu; Huan Xi; Siyuan Liu; Yatao Wang; Lu Yang; Cong Han; Xingxing Zheng; Hao Wang; Songjian Huang; Wenfang Zhang (Molecular Neurobiology, 2026)

Time-Resolved Oxidative Stress and Apoptosis in Murine Retina under Acute Hypobaric Hypoxia with Parallel Activation of the LIF–JAK–STAT3 Axis - Hao Wang; Qiang Ye; Songjian Huang; Keke Ge; Cong Han; Huan Xi; Junyi Qiao; Jingrong Feng; Peirun Wu; Yuhan Bao; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Integrated multi-trophic aquaculture of sandfish Holothuria scabra with hard clam Meretrix taiwanica and milkfish Chanos chanos under environmental stress - Po-Kun Tseng; Min-Luen Tsai; Li-Xi Xu; Meei-Mei Chen; Yin-Hao Lai; Yu-San Han; Feng-Jie Su (Aquaculture International, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The PpEIL2/3-PpWRKY45A/B-PpMIF2 transcription cascade regulates ethylene-induced filament senescence in peach - Charmaine Ntini; Sylvia Cherono; Huasheng Huang; Beatrice Nyambura Njuguna; Juanli Sun; Yudi Liu; Wen Xiao; Beibei Zheng; Ruo-Xi Zhang; Yunpeng Cao; Yuepeng Han; Yun Zhao (Postharvest Biology and Technology, 2025)

9-Methylstreptimidone: A novel promising fungicide disrupting material metabolism and energy synthesis in Colletotrichum orbiculare - Wenshuai Song; Jingzheng Sun; Haifeng Zhang; Han Wang; Lifeng Guo; Xiaoya Fan; Xi Xu; Kun Zhang; Hongbo Pang; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Pesticide Biochemistry and Physiology, 2025)

Integrated modeling of urban flood inundation and pollutant transport considering building-scale exchanges - Congji Han; Kenji Kawaike; Takahiro Koshiba; Keiko Wada; Xi Chen; Liming Liu (Journal of Hydrology, 2025)

Environmental impacts of rare earth elements mining and strategies for sustainable management: A comprehensive review - Yong-He Han; Xi-Wen Cui; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2025)

Anthropogenic gadolinium as an emerging contaminant in megacity rivers: Sources, fluxes, and policy implications in North China - Xi Gao; Guilin Han; Shitong Zhang; Jie Ren (Journal of Environmental Management, 2025)

Combined toxicity of cesium and uranium on cyanobacterial growth and metabolism: Mechanisms and implications - Meng-wei Han; Xu Yang; Bin Dong; Jin-long Lai; Hai-ling Xi; San-ping Zhao (Journal of Environmental Chemical Engineering, 2025)

Solvent-based recycling of PC and ABS from e-waste: Efficiency, economics, emissions reduction, and job opportunities - Han Gao; Xi-Ming Zeng; Hong-Gang Ni (Journal of Environmental Management, 2025)

Treatment optimization and working mechanism analysis of Pb(II) removal from printed-circuit board wastewater using 3-hydroxybenzoic acid-modified copper metal - Shuai Luo; Dengxiang Fan; Lequn Sun; Miaomiao Yang; Weiwei Xi; Han Zhang; Liu Jiang; Rongfang Yuan; Beihai Zhou; Huilun Chen (Journal of Environmental Chemical Engineering, 2025)

Electrochemically assisted activation of peroxymonosulfate by Cu-Co bimetallic carbon nitride for enhanced deoxynivalenol degradation - Bingjie Wang; Xi Zhang; Zhixia Wu; Chenyu Li; Jingfeng Wang; Xu Han (Journal of Environmental Chemical Engineering, 2025)

Retraction notice to ‘Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis’ [Environ. Res. 241 (2024) 117474] - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

Harnessing dental stem cell-extracellular vesicles for osteogenesis, immunomodulation, angiogenesis, and neurogenesis during bone regeneration - Xi Xiang; Jianwen Li; Danyuan Xie; Keyu Lv; Hanyang Yu; Xinwei Han; Ying Ruan; Tingting Sun; Xuguang Gao; Youguang Lu; Janak L. Pathak; Sujuan Zeng (Chemical Engineering Journal, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

Synergistic interfacial engineering and ion transport kinetics in high-safety PEO-based polymer electrolytes - Hong-Yu Wang; Kun-Rong Lu; Yue-Xi Han; Fa-Nian Shi; Peng-Fei Wang; Yu-Hang Zhang (Chemical Engineering Journal, 2025)

Cyclodextrin polyrotaxane based self oxygen supplying nanoparticles for enhancing the sonodynamic therapy mammary cancer performance with a “one-stone-two-birds” strategy - Yongyan Sun; Kaixuan Luo; Xi Zhu; Moxian Chen; Yuting Sun; Han Wang; Yunxiao Yang; Jianmei Yang; Guixi Wang; Jin Zhang; Jin Yan; Junnan He; et al. (Carbohydrate Polymers, 2025)

Pan-genomic insights into RLK family evolution and adaptation in Dioscorea alata - Zhi-Yan Wei; Sai-Xi Li; Ming-Han Li; Jie Tang; Yu-Qian Jiang; Xin-Yu Lu; Yan-Mei Zhang; Jia-Yu Xue (Plant Molecular Biology, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

Piezo1 in heart failure: A new perspective from cytomechanical sensing to diverse cellular pathways - Jia-yan Wang; Bo-han Li; Chang-yu Liu; Qian-he Wang; Jie Wang; Mao-juan Guo; Xi-juan Jiang (Molecular Biology Reports, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Disulfidptosis-related genes RPN1 inhibits the progression of hepatocellular carcinoma by regulating cell cycle, may be a new therapeutic targets - Rongzheng Zhang; Kun Zhou; Meng Wu; Han Qiao; Le Yu; Xi Jin; Jingbo Li; Guanglu Dong; Shuyun Zhang (Inflammation Research, 2025)

Blocking triggering receptors expressed on myeloid cell-1 alleviates alveolar epithelial cell senescence by inhibiting oxidative stress in pulmonary fibrosis - Wen-Jing Zhong; Jian-Bing Xiong; Chen-Yu Zhang; Ling Jin; Nan-Shi-Yu Yang; Han-Xi Sha; Yu-Biao Liu; Jia-Xi Duan; Cha-Xiang Guan; Yong Zhou; Feng Su (Histochemistry and Cell Biology, 2025)

Carnosol attenuates Ang II-induced renal injury by p62-KEAP1-NRF2 signaling pathway - Shijie Fan; Ying Zhao; Qingqing Zhao; Diyun Xu; Xi Chen; Jibo Han; Ziming Fang; Guang Liang; Yunjie Zhao (Toxicology and Applied Pharmacology, 2025)

Numerical study of Bragg resonance reflection for wave energy converter arrays in a two-dimensional viscous wave tank - Hongjian Wu; Hongda Shi; Feifei Cao; Mingqi Yu; Meng Han; Xi Yi; Jiajun Chen (Ocean Engineering, 2025)

Design of 3-hydroxybenzoic acid-modified Cu₃(BTC)₂ for improved adsorption of Pb²⁺ and Cd²⁺ from water: characterization and mechanism - Shuai Luo; Dengxiang Fan; Lequn Sun; Miaomiao Yang; Weiwei Xi; Han Zhang; Liu Jiang; Rongfang Yuan; Beihai Zhou; Huilun Chen (Journal of Water Process Engineering, 2025)

Electrodeposited WO3-carbon felt electrodes for electrochemical recovery of copper from PCB wastewater: Behavior and mechanism - Dengxiang Fan; Yunlong Dong; Lequn Sun; Jingtao Sun; Han Zhang; Miaomiao Yang; Weiwei Xi; Liu Jiang; Rongfang Yuan; Beihai Zhou; Huilun Chen; Shuai Luo (Journal of Water Process Engineering, 2025)

Cholesterol metabolism as a key target in triphenyl phosphate-induced testosterone biosynthesis disorder: Implications for male reproductive health - Yuhan Ma; Dihui Xu; Zongli Huo; Xi Wang; Yabing Chen; Xiaodong Han (Journal of Hazardous Materials, 2025)

Revealing dissolved inorganic carbon sources and water quality in megacity rivers by Bayesian model and Fuzzy comprehensive evaluation - Xi Gao; Guilin Han; Shitong Zhang; Jie Ren; Jinke Liu (Journal of Cleaner Production, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Morphological, productivity and grain quality characteristics and evolutionary trends of wheat cultivars in different ecological regions of China in the past decades - Rui Nan; Jiawei Zhang; Shuaijie Han; Shaoqi Wu; Gaijuan Tang; Xiaofeng Zhao; Baolin Wu; Xiaohong Chen; Fengli Sun; Yajun Xi; Chao Zhang (Journal of Cereal Science, 2025)

Photodynamic bacterial inactivation by a ferulic acid-based hydrogen-bonded photoactive edible coating for fresh fruit preservation - Shuo Shi; Xi Lan; Xiyan Ding; Liping Wang; Ximei Han; Jing Sun; Jianlong Wang; Jinyou Duan (Food Chemistry, 2025)

Enhancing energy efficiency in CO2-rich amine solution regeneration using a Cu-modified attapulgite catalysts - Dong Liu; Zelu Zhou; Zhitao Han; Mengjing Zhang; Aicheng Song; Xi Wu; Xiao Yang; Dong Ma (Environmental Research, 2025)

Multi-omics and random forest reveal lipid metabolism disruption and biomarkers in grass carp (Ctenopharyngodon idellus) exposed to 2-methylisoborneol - Huan Han; Jun-Ming Zhang; Kang Li; Justice Frimpong Amankwah; Xiang-Biao Zeng; Zi-Qian Shen; Xi-Chen Jin; Tao-Ying Chen; Jing-Wei Liu; Li-Ping Liu (Environmental Research, 2025)

Optimizing lithium extraction from brines using fluoride-doped lithium titanate in hybrid capacitive deionization - Jiahui Zhang; Wen Xi; Jianing Hu; Qingqing Han; Youfang Zhang; Shuo Huang; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Desalination, 2025)

Modification of starch traits in commercial wheat through TaWaxy gene editing - Yuliang Qiu; Xi Li; Ming Fan; Huali Tang; Shuangxi Zhang; Weihong Huang; Zhiyang Han; Surong Wang; Hao Peng; Yonggui Xiao; Xingguo Ye; Ke Wang (Carbohydrate Polymers, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

Genome-wide identification and expression analysis of NRT2 gene family in Tartary buckwheat suggests the potential role of FtNTR2.4 in low nitrogen response - Daiying Xu; Yaoxuan Zou; Nan Hu; Han Li; Junjie Yin; Jiting Wang; Xi Wu; Dabing Xiang; Jianglin Zhao; Xiaoqin Zheng; Yan Wan; Yanxia Liu; et al. (Physiology and Molecular Biology of Plants, 2025)

Fungicide, not nitrogen, reduces soil nematode diversity and multifunctionality in alpine grasslands - Yali Zhang; Hao Xi; Joann K. Whalen; Jiayao Han; Xiang Liu; Yongjun Liu (Applied Soil Ecology, 2025)

Key drivers and feedback of soil-water microbial communities and resistance gene in a decommissioned uranium-containing polymetallic mine - Yangyue Pei; Xiangyu Xi; Zhilin Wang; Yun Sun; Xinyi Chen; Ying Han; Faqin Dong; Lei Zhou (Journal of Hazardous Materials, 2025)

Anthropogenic gadolinium as a tracer of urban impact in the Chinese Capital Economic Circle: Distribution, sources, and sustainable remediation perspectives - Xi Gao; Guilin Han; Shitong Zhang; Jie Ren (Journal of Hazardous Materials, 2025)

Nanoplastics reshape lipid metabolism in marine microalgae with potential ecological consequence - Yajing Liu; Tianle Xi; Jia Liu; Han Jiang; Xiaowen Zhang; Naihao Ye; Chengwei Liang (Journal of Hazardous Materials, 2025)

Bimetallic ion location and their synergistic effect on arsenic adsorption in fly ash based-modified zeolite: Experimental and simulation approaches - Xiangang Wu; Yong Han; Liyun Yang; Le Xi; Shilong Jia; Kaixin Chen; Jin Zhang; Hao Bai; Tetsuya Nagasaka (Journal of Environmental Chemical Engineering, 2025)

Influence of calcination temperature on catalytic performance of Cu-Zn bimetallic MOFs derivatives for electroreduction CO2 to ethylene - Dong Liu; Xiao Yang; Zhitao Han; Xi Wu; Zelu Zhou; Mengjing Zhang; Aicheng Song; Dong Ma (Journal of Environmental Chemical Engineering, 2025)

Enhancing CO2 capture efficiency of K2CO3 solution with quaternary ammonium additives - Mengjing Zhang; Zhitao Han; Aicheng Song; Dong Liu; Zelu Zhou; Xi Wu; Xiao Yang; Dong Ma (Journal of Environmental Chemical Engineering, 2025)

Nannoplankton response indicates intra-OAE2 cooling (Plenus Cold Event) in southeastern Tethys (Qiangdong, Tibet) - Yi Zhang; Hanwei Yao; Paul R. Bown; Huifang Guo; Kaibo Han; Cinzia Bottini; Chengshan Wang; Xi Chen (Global and Planetary Change, 2025)

Trade-offs between decreasing subsidies and sustaining clean heating targets considering households’ income heterogeneity in rural China - Na Li; Xi Luo; Yanhu Han (Energy and Buildings, 2025)

Coordinated optimization and regulation of rural residential flexible loads and agricultural machinery energy storage batteries considering battery life degradation - Xi Luo; Yanning Zheng; Mingyue Han; Wenyuan Huang (Energy and Buildings, 2025)

Spatiotemporally-graded BHP/G@met scaffold system enables sequential angiogenesis-osteogenesis coupling for accelerated bone regeneration - Han Zhang; Shuqing Chen; Guodong Zhang; Yongbin Wang; Zichen Cui; Fei Chen; Yukun Du; Guanghui Gu; Tianyu Bai; Changlin Lv; Wenkang Yang; Shiqi Xu; et al. (Chemical Engineering Journal, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Chemotaxonomic significance of chemical constituents from Ligia exotica, sea slater - Yue-Yao Li; Fei-Hua Yao; Qian Han; Jin-Li Luo; Xin-Yue Li; Cheng-Hai Gao; Xiang-Xi Yi (Biochemical Systematics and Ecology, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Migration and phototransformation of additives in plastic products: A case study of advertising banners - Xi Chen; Zhongyu Guo; Tong Xu; Wenjing Han; Qing Xie; Huaijun Xie; Xiaofan Li; Jingwen Chen (Science of The Total Environment, 2025)

Fungal diversity associated with cherry leaf spot in Yantai city, Shandong province, China - Yumeng Wang; Ting Liu; Chuang Han; Xiaoyan Yu; Xi Xu; Yuhan Guo; Xinying He; Wensheng Xiang; Xiangjing Wang; Junwei Zhao (Physiological and Molecular Plant Pathology, 2025)

Enclosed-terrain urbanized areas require vertically stratified air quality management: Insights from particulate matter vertical observations in China's Sichuan Basin - Xi Shu; Xue Qiao; Ya Tang; Philip K. Hopke; Qi Ying; Junfeng Wang; Bin Han; Zhongjun Xu; Zhonglin Xia; Yinhong Ma; Yuan Dai; Jun Leng (Journal of Environmental Management, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

A Comparative Analysis of Subtyping Methodologies on Cross-sectional sMRI Data - Shirui Zhang; Baitong Zhang; Kun Zhao; Zhuangzhuang Li; Pan Wang; Dawei Wang; Chengyuan Song; Jie Lu; Zengqiang Zhang; Hongxiang Yao; Tong Han; Chunshui Yu; et al. (Neuroscience Bulletin, 2025)

Cerebrospinal Fluid CCL25 as a Biomarker for Alzheimer's Disease: Associations with Pathology, Neurodegeneration, and Cognitive Decline - Yu-Han Chen; Zhi-Bo Wang; Xi-Peng Liu; Zhi-Qi Mao (Molecular Neurobiology, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

Indication of triple oxygen isotopes to replenishment mechanisms and evaporation processes in Yongding River Basin, North China - Yaxin Zhu; Guilin Han; Di Wang; Shitong Zhang; Xi Gao (Applied Geochemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enriching population diversity in neuroscience - Ziteng Han; Guoyuan Yang; Tiantian Liu; Shintaro Funahashi; Xi-Nian Zuo; Tianyi Yan (Science Bulletin, 2025)

Association of microplastics in human cerebrospinal fluid with Alzheimer’s disease-related changes - Ping He; Feng Wang; Guangjun Xi; Yang Li; Fengyun Wang; Hui Wang; Lei Li; Xuemei Ma; Yan Han; Yachen Shi (Journal of Hazardous Materials, 2025)

Component-level life cycle carbon emission analysis and multi-objective optimization with power characteristics for an adaptively-coupled solar ejector-compression refrigeration system - Yingjie Xu; Jiedong Wang; Jianfeng Mao; Xi Shen; Xiaohong Han; Guangming Chen (Journal of Cleaner Production, 2025)

Global, regional and national burden of lung cancer attributable to PM2.5 air pollution: Trends from 1990 to 2021 with projections to 2045 - Yingfan Deng; Zengbin Li; Pan Zhang; Yang Yang; Yuhan Xie; Yutong Cheng; Shuiyan Yu; Guixian Zhu; Lili Han; Lijun Jia; Wentao Xi; Pei Wang; et al. (Journal of Environmental Management, 2025)

Spatiotemporal patterns and driving factors of ecological restoration regions: Insights from multi-scale analysis - Yuhang Zhang; Zhenqi Hu; Jiazheng Han; Xizhao Liu; Zhanjie Feng; Xi Zhang (Environmental Impact Assessment Review, 2025)

CO2 enrichment enhances biomass density and C:N:P ratios in phytoplankton assemblage in the coastal water of the Taiwan Strait - Yumeng Pan; Xiang Yang; Jinlong Shang; Xi Liu; Yinrui Wang; Junqin Cai; Yubin Hu; Kui Xu; Zhengke Li; Yonghe Han; Hong Zhang; Hun Xue; et al. (Journal of Applied Phycology, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Evidence for elevated wildfire activity during Cretaceous OAE 2 from eastern Tethys - Shuai Shi; Xi Chen; Huifang Guo; Hanwei Yao; Kaibo Han; David B. Kemp; Shengbao Shi; Zhong Han; Chengshan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Deep transfer learning for spatiotemporal mapping of PM2.5 nitrate across China: Addressing small data challenges in environmental machine learning - Xi Zheng; Haiyan Meng; Zixiang Zhao; Xinyi Liu; Li Zhou; Michael L. Grieneisen; Han Zhang; Yu Zhan; Fumo Yang (Journal of Hazardous Materials, 2025)

Corrigendum to “High-resolution organic carbon isotope chemostratigraphy of the lower Aptian and the expression of Oceanic Anoxic Event 1a in the Tibetan Himalaya” [Global and Planetary Change 248C (2025), 104759] - Kaibo Han; Zhiqin Liu; Xi Chen; Xuan Liu; Huifang Guo; Hanwei Yao; Yi Zhang; David B. Kemp; Chengshan Wang (Global and Planetary Change, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

NLRC3 regulates RIP2, STING, TBK1, and TRAF6 mediated type I IFN signaling and inflammatory response in large yellow croaker Larimichthys crocea - Yu Qing Xu; Ying Li; Kun Huang Han; Jia Xi Zhang; Kai Qing Li; Jing Jiang; Zhao Han Sun; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2025)

A high-performance wearable microneedle sensor based on CNT/CCNT@Cu-ZIF-67 composites for simultaneous detection of uric acid and dopamine - Jiachen Zhu; Weiliang Wang; Luwen Wang; SongYa Cui; Dongxue Han; Shuting Liu; Shaopeng Ma; Shangbin Xi; Wei Cai; Liang Peng (Chemical Engineering Journal, 2025)

Defect-triggered phase transition energizes the defects in non-stoichiometric molybdenum sulfide for catalyzing polysulfide conversion in lithium sulfur batteries - Haojie Li; Kai Xi; Ce Yang; Han Jin; Kunming Pan; Xuetao Wang; Saifei Pan; Diandian Han; Xueping Gao; Guoran Li (Chemical Engineering Journal, 2025)

Chiral stationary phase based on chitosan Schiff base derivatives for enantioseparation - Jing He; Jiangbo Xi; Bowen Han; Qi Xiao; Dandan Guo; Shaohua Huang (Carbohydrate Polymers, 2025)

PCBP2 in gastrointestinal cancers: fundamental mechanism and clinical potential - Chenyang Wang; Xi Chen; Lili Duan; Junfeng Chen; Liaoran Niu; Siyu Wei; Han Bai; Yujie Zhang; Wei Zhou; Jinqiang Liu; Wanli Yang; Yu Han; et al. (Journal of Molecular Medicine, 2025)

Sex effects on dynamic structure–function coupling of intrinsic brain network - Xi Zhang; Dandan Li; Yuting Yuan; Xuebing Han; Lan Yang; Jiayu Lu; Ting Li; Zhifeng Li; Bin Wang (Brain Imaging and Behavior, 2025)

Editorial Expression of Concern: Salt-Rich Selenium for Prevention and Control Children with Kashin–Beck Disease: a Meta-analysis of Community-Based Trial - Fang-fang Yu; Jing Han; Xi Wang; Hua Fang; Huan Liu; Xiong Guo (Biological Trace Element Research, 2025)

Megacity river as a critical anthropogenic source of strontium release in global Sr cycle: Insights from Bayesian mixing model and Sr isotope - Shitong Zhang; Guilin Han; Xi Gao; Jinke Liu; Nan Qiao (Water Research, 2025)

Role of biogas stirring in alleviating acidification and promoting methanogenesis during the anaerobic digestion of food waste: Macroscale and microscale perspectives - Yi Han; Guangcheng Xiong; Si Yang; Xi Luo; Feixiang Zan; Xiaohui Wu; Guanghao Chen (Waste Management, 2025)

Environmentally relevant concentrations of antimony pose potential risks to human health: An evaluation on human umbilical vein endothelial cells - Shanshan Wang; Dongqian Guo; Xian Chen; Su-Zhu Chen; Xi-Wen Cui; Yong-He Han; Ping Xiang (Toxicology in Vitro, 2025)

Lithospheric electrical structure of Zhenghe-Dapu fault in South China determined by multi-geophysical observations: Implications for geothermal mechanism - Song Han; Liuyang Xu; Xipeng Shan; Xi Xu; Xingtao Kuang; Yanyun Sun; Baodi Wang (Tectonophysics, 2025)

Impacts of glacier shrinkage on peak melt runoff at the sub-basin scale of Northwest China - Min Xu; Pengshou Wang; Xi Zhang; Tao Ma; Junliang Jin; Shichang Kang; Haidong Han; Hao Wu; Zhikang Hou; Xingdong Li; Xiaodong Wu (Journal of Hydrology, 2025)

Mechanistic study of ultrasound synergy with soybean 11S globulin to improve myofibrillar protein gel properties in low-salt lamb: molecular conformation and water migration - Rong Bai; Jing Xi; Huiyu Han; Rakhimova Aidana; Aitmagambetova Madina; Shengqi Jiang; Xiang Ye; Chunjie Yang; Siying Wang; Wu Ding (Food Research International, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Design and analysis of CFETR magnet current feeder - Quan Han; Yuntao Song; Kun Lu; Weibin Xi; Chen Liu; Kaizhong Ding; Qingquan Zhang; Xufeng Liu; Shuangsong Du; Jinxing Zheng (Annals of Nuclear Energy, 2025)

The effect of safety culture on the safety behavior of ship deck officers- empirical evidence from shipping industry - Yongtao Xi; Zhijie Wang; Shenping Hu; Bing Han; Jingbo Yin (Frontiers in Marine Science, 2025)
Introduction The creation of safety culture in shipping industry is an important measure for reducing ship accidents and improving navigation safety. On the basis of literature review and theoretical assessments, this paper puts forward the conceptual logical framework and research hypotheses of safety culture and safety behavior. The purpose of this paper is to explore the effect of safety culture on ship officers' safety behavior. Method This paper developed a scale by referring to the well-established safety culture and safety behavior scales proposed in previous literature and combined with the shipping background. Based on self-reported questionnaire and primary data collected from 229 deck officers and captains from a shipping company in Shanghai, a relationship model between safety culture and safety behavior was constructed using structural equation modeling (SEM), and empirical tests were conducted to explore the impact of safety culture on ship officers’ safety behavior. Results The results show that safety culture has a positive impact on ship officers’ safety behavior, in which safety material culture has a positive impact on safety compliance behavior, safety system culture has positive impacts on safety compliance behavior and prosocial safety behavior, while safety management culture and safety value fit have positive impacts on all dimensions of ship officers’ safety behavior. Discussion This paper proposes and validates a new model that can help explore the impact of safety culture on the safety behavior of ship officers. The research results indicate that we can improve ship officers’ safety behavior from two dimensions: safety management culture and safety value fit. More importantly, the research findings can help shipping companies develop measures to improve ship officers’ behavior based on their own circumstances, thereby reducing the likelihood of maritime accidents. The results of this paper will contribute to the development of safety management in shipping industry.

Experimental study of pressure distribution and wave forces on pile groups under extreme waves - Xi Yu; Jiajia Wang; Wanshui Han; Lili Xiao; Xin Xu; Kai Zhou; Silu Che; Xiaokun Chen; Mengqi Xia (Ocean Engineering, 2025)

Newly isolated bacterium and arbuscular mycorrhizal fungus effectively reduce the root cadmium concentration and increase the root biomass of Ophiopogon japonicus - Lin Lin; Jin Li; Obey Kudakwashe Zveushe; Ying Han; Hengxing Zhang; Yu Qin; Victor Resco de Dios; Lei Zhou; Xiangyu Xi; Wei Zhang; Yulian Zhao; Amal Mohamed Omer; et al. (Journal of Hazardous Materials, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

High-resolution organic carbon isotope chemostratigraphy of the lower Aptian and the expression of Oceanic Anoxic Event 1a in the Tibetan Himalaya - Kaibo Han; Zhiqin Liu; Xi Chen; Xuan Liu; Huifang Guo; Hanwei Yao; Yi Zhang; David B. Kemp; Chengshan Wang (Global and Planetary Change, 2025)

Selective adsorption of Rb+ and Cs+ by a superparamagnetic Fe₃O₄@FeMn-MOF from brine - Yanping Wang; Qiongyuan Zhang; Dezhen Fang; Kexin Li; Zhongmei Song; Wenjie Han; Junwei Li; Xiushen Ye; Haining Liu; Huifang Zhang; Xi Zhang; Zhijian Wu (Desalination, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Tim-3 Deficiency Ameliorates Motor Deficits and Neuroinflammation in MPP+/MPTP-Induced Parkinson’s Disease Models via the NF-κB/NLRP3 Pathway - Xi Yin; Ge Li; Fei Ji; Miao Wang; Yang Gao; Fengzhu Li; Zhenfu Wang; Gencheng Han; Zhongbao Gao (Molecular Neurobiology, 2025)

Effects of pile groups and wave dynamics on the hydrodynamic load of offshore pile caps - Kai Zhou; Jiajia Wang; Wanshui Han; Lili Xiao; Xin Xu; Yuheng Xiang; Xi Yu (Ocean Engineering, 2025)

Fertilization-recruited Actinomycetota enhances nutrient and energy metabolisms to favor plant growth and arsenic accumulation in Pteris vittata - Yong-He Han; Yi-Xi Li; Xi-Wen Cui; Ying Zhu; Hong Zhang; Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Deciphering the mechanistic insight into modified biochar for distinct anaerobic digestion processes: Surface functional groups and electron-transmitting capabilities - Yi Han; Yaoyihan Luo; Lu Zhang; Xiejuan Lu; Xi Luo; Xiaohui Wu; Feixiang Zan (Journal of Environmental Chemical Engineering, 2025)

Degradation of carbaryl by UV/chlorine process: Optimal degradation conditions, reaction intermediates, and mechanisms - Ayoung Choi; Jungyeon Kim; Haesung Lee; Minhee Kim; Xi-Zhi Niu; Bineyam Mezgebe; Mallikarjuna N. Nadagouda; Abdulaziz Al-Anazi; Changseok Han (Chemical Engineering Journal, 2025)

In-situ pore forming bone adhesives targeting disordered osteoimmune microenvironment and bone metabolic balance to promote osteoporotic fracture healing - Haiyue Zhao; Lingjun Wang; Kun Xi; Wei Wang; Xinzhao Jiang; Jiahao Wang; Liang Zhou; Wenbo Wang; Feng Cai; Meng Han; Jincheng Tang; Yu Feng; et al. (Chemical Engineering Journal, 2025)

Vegetation restoration affects soil erosion processes by altering the soil net force - Mao Qiu; Xiangjun Pei; Renji Zhang; Xiaochao Zhang; Hongchao Xi; Xiaoyi Zhao; Jie Du; Jining Zhang; Boyu Han (CATENA, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Numerical modeling and analysis of GNSS carrier-phase diffraction error in occlusion environments - Ruijie Xi; Luming Han; Qusen Chen; Weiping Jiang; Xiaolin Meng; Xiangdong An; Wei Xuan (Journal of Geodesy, 2025)

De novo design of dual-detection fluorescent sensors for bisulfite and copper (II) ion based on cascade activation - Tian Tan; Wenyu Xi; Chenxu Duan; Ying Han; Peikun Xiao; Hongqi Yin; Hong Huang; Xulang Chen; Yanjun Hu; Xiaohuan Huang (Analytica Chimica Acta, 2025)

Effects of grazing on temperate grassland ecosystems: A meta-analysis - Chaofeng Shen; Jun Zhang; Xi Yang; Juhong Liu; Guodong Han (Agriculture, Ecosystems & Environment, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Itaconate promotes mitophagy to inhibit neuronal ferroptosis after subarachnoid hemorrhage - Guijun Wang; Zhijie Li; Wenrui Han; Qi Tian; Chengli Liu; Shengming Jiang; Xi Xiang; Xincan Zhao; Lei Wang; Jianming Liao; Mingchang Li (Apoptosis, 2025)

Ratio Fluorescence Sensor Based on Bimetal MOFs for the Detection of Hg2+and H2O2 - Bo-Ming Han; Hao-Rui Zhang; Wen-Jie Gao; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Fluorescence, 2025)

A multi-level monitoring mechanism for inland ships sewage based on software-defined cloud-edge-end collaborative architecture - Dong Han; Hualong Chen; Yuanqiao Wen; Changshi Xiao; Xiaodong Cheng; Xi Huang (Ocean & Coastal Management, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Plasticization of gelatin/chitosan films with deep eutectic solvents and addition of Flos Sophora Immaturus extracts for high antioxidant and antimicrobial - Quanling Zhao; Xi Huang; Lijun Qian; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Zhiyong Qin (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Analysis of atmospheric pollution transport using aerosol optical depth remote sensing data and the optical flow method - Botao He; Xi Lu; Yong Xue; Wenhao Liu; Shuhui Wu; Peng Wang; Pei Li; Liying Han (Atmospheric Pollution Research, 2025)

Application of dielectric properties for identification of normal and malignant gastrointestinal tumors and lymph nodes ex vivo - Xi Rao; Qianyun Chen; Lishan Ding; Noman Shahid; Sidra Wafa; Qiang Huang; Enming Qiu; Xi Zhang; Songsheng Wang; Xueer Xia; Shuai Han; Haijin Chen; et al. (Physical and Engineering Sciences in Medicine, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Gyral peak variations between HCP and CHCP: functional and structural implications - Guannan Cao; Songyao Zhang; Zhibin He; Zifan Wang; Lei Guo; Zhiqiang Yan; Junwei Han; Xi Jiang; Tuo Zhang (Brain Structure and Function, 2025)

T-2 toxin triggers immunotoxic effects in goats by inducing ferroptosis and neutrophil extracellular traps - Jing Huang; Kaifeng He; Xin Guo; Jiaxuan Wang; Han Hu; Xuhui Zhang; Na Guo; Yiwen Wang; Wenlong Huang; Rongsheng Huang; Tingting Liu; Xi Jiang; et al. (Toxicology and Applied Pharmacology, 2025)

Neoarchean orogenic belt evolution in the northeast North China Craton: Implications for the reconstruction of early Earth’s microplates - Guozheng Sun; Shuwen Liu; Sanzhong Li; Timothy M. Kusky; Fangyang Hu; Han Bao; Lei Gao; Yalu Hu; Shengyao Yu; Liming Dai; Lintao Wang; Xi Wang (Precambrian Research, 2025)

Vertical canopy structure dominates cooling and thermal comfort of urban pocket parks during hot summer days - Si-Qi Zhou; Zhao-Wu Yu; Wei-Yuan Ma; Xi-Han Yao; Jun-Qi Xiong; Wen-Juan Ma; Shu-Yao Xiang; Qi Yuan; Ying-Ying Hao; Dong-Fan Xu; Ben-Yao Wang; Bin Zhao (Landscape and Urban Planning, 2025)

An environmentally friendly and highly efficient PBS composite membrane prepared by TiO2 hybridization and PDA surface coating - Yanhong Ji; Xiaodie Liu; Xi Liu; Quan Li; Zunbo Han; Hang Zhao; Zixing Zhou; Hanyu Shi; Benqiao He (Journal of Environmental Chemical Engineering, 2025)

Cation-doping tuned flower-like Co-based spinel structure for methane combustion: Structure-effect and reaction pathway confirmation - Xi Zhang; Shuo Yao; Mingjuan Han; Nengjie Feng; Hui Wan; Guofeng Guan (Fuel, 2025)

Inhibitory effects of κ-carrageenan oligosaccharides on histamine formation in Atlantic mackerel (Scomber scombrus) during cold storage - Zilong Guo; Xiao Feng; Jiaheng Han; Tian Zhong; Zekai Zheng; Ying Xiao; Xi Yu (Food Bioscience, 2025)

Polycyclic aromatic hydrocarbons exposure in early pregnancy on child neurodevelopment - Zhi Li; Yu Han; Xinyu Li; Wenjuan Xiong; Tingkai Cui; Wei Xi; Shihao Jin; Xin Zhang (Environmental Pollution, 2025)

A weakly supervised soil pore segmentation method based on traditional segmentation algorithm - Yinkai Fu; Zihan Huang; Yue Zhao; Benye Xi; Yandong Zhao; Qiaoling Han (CATENA, 2025)

Mapping and validation of QTkw.cau-3DL, a major QTL controlling thousand-kernel weight in wheat - Xi He; Jilu Liu; Xiaomeng Ren; Shurong Wei; Zhenzhen Zhu; Fuping Zhang; Sijia Hu; Yanpeng Ding; Fangyao Sun; Dong Han; Guihua Bai; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Deciphering the landscape and evolutionary trajectory of NLR immune receptors in Dioscorea alata - Yue Wang; Xing-Yu Feng; Wen-Qiang Wu; Ming-Han Li; Sai-Xi Li; Zhen Zeng; Zhu-Qing Shao; Yan-Mei Zhang (Plant Molecular Biology, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Medium modification of Cynanchum wilfordii adventitious root culture for the production of C21 steroidal glycosides, polysaccharides, and polypeptides using orthogonal design methods - Han-Xi Li; Yu-Qing Guo; Wei-Qi Ye; Zhong-Yu Zhou; Ling-Hong Bai; Xuan-Chun Piao; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2025)

Pilot-scale experimental study on the enhanced natural attenuation of complex organic contaminants based on the recharge of electron acceptors - Shuxuan Wu; Yu Yang; Xu Han; Sheng Deng; Jiayu Kang; Beidou Xi; Yonghai Jiang (Water Research, 2025)

Environmental drivers of sediment accumulation in urban sewer systems: A case study of Kyoto City, Japan - Liming Liu; Kenji Kawaike; Keiko Wada; Takahiro Koshiba; Xi Chen; Congji Han; Haruki Matsui (Water Research, 2025)

The instabilities of the Antarctic slope current in an idealized model - Chengyan Liu; Zhaomin Wang; Xi Liang; Xiang Li; Xianxian Han; Wenjin Sun; Yang Wu; Xichen Li; Chen Cheng (Journal of Marine Systems, 2025)

Distribution and controlling factors of dissolved inorganic carbon in urban rivers of a North China megacity: Insights from δ13CDIC - Jie Ren; Guilin Han; Jinke Liu; Shitong Zhang; Xi Gao (Journal of Environmental Management, 2025)

Comparison of product distribution and property among distiller’s grains pyrolysis and partial gasification in different atmospheres for adapting to two-stage gasification process - Duo Sun; Fang Wang; Xi Zeng; Weini Peng; Guannan Cui; Chao Wang; Zhennan Han; Guangwen Xu (Fuel, 2025)

Progress and challenges of spinel materials for catalytic combustion of methane - Xi Zhang; Xiaodi Zhang; Lingling Ren; Mingjuan Han; Nengjie Feng; Hui Wan; Guofeng Guan (Fuel, 2025)

Multi-scale doping-Induced impedance matching of graphene aerogel enables ultra-broadband microwave absorption - Lingling Tan; Xi Chen; Ruiheng Han; Xianzhang Wu; Shengrong Yang; Jingxia Huang (Chemical Engineering Journal, 2025)

Isoalcanivorax beigongshangi sp. nov., isolated from the fermented grains of Chinese baijiu - Tong-Xi Zhang; Yi-Ming Li; Hao-Yue Gu; Ru Zhang; Zhan-Bin Sun; Han-Xu Pan; Qing Ren (Antonie van Leeuwenhoek, 2025)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Characteristics and health risks assessment of PM2.5-bound heavy metals during winter in urban areas of northern China: A case study in Kaifeng - Xin Qi; Yan Han; Hanxiong Che; Jiawei Zhou; Chao Peng; Zhier Bao; Yiliang Liu; Lingshuo Meng; Shumin Zhang; Fumo Yang; Wenbo Xue; Yu Lei; et al. (Science of The Total Environment, 2024)

Dual-directional regulation of extracellular respiration in Shewanella oneidensis for intelligently treating multi-nuclide contamination - Xin-Lu Cai; Xuan Yao; Li Zhang; Yu-Han Chai; Xuan Liu; Wen-Wen Liu; Ruo-Xi Zhang; Yang-Yang Fan; Xiang Xiao (Journal of Hazardous Materials, 2024)

Bioinspired interlaced wetting surfaces for continuous on-demand emulsion separation - Hanpeng Gao; Haiyu Qian; Zong Meng; Siyu Chang; Xi Wang; Zhiwu Han; Yan Liu (Journal of Hazardous Materials, 2024)

Preparation and characterization of nano-sized biological FeS for the removal of V(V) from aqueous solutions - Xiangyu Xi; Xuan Hu; Zhilin Wang; Faqin Dong; Ying Han; Zhiqin Zheng; Lei Zhou (Journal of Environmental Chemical Engineering, 2024)

Heat-dynamics network model and energy analysis of a miniature free piston Stirling cryocooler for application of high operating temperature infrared detector - Zhongli Xi; Xiaoqing Zhang; Han Jiang (International Journal of Refrigeration, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Optimizing tomato waste hydrolysate for enhanced fucoxanthin biosynthesis in mixotrophic cultivation of Isochrysis galbana - Xi-Wen Fan; Han Sun; Derek M. Ayittey; Zhi-gang Zhou; Carol Sze Ki Lin; Tao Tang; Zheng Sun (Bioresource Technology, 2024)

The effect of COVID-19 epidemic and sandstorm on distribution of short-, medium-, and long-chain chlorinated paraffins in outdoor atmosphere of Xi'an, Northwest China - Xiuqun Liu; Xiaomei Huang; Han Song; Jingzhi Wang; Jiayu Li; Xi Li; Zhibao Dong; Li Xing; Junji Cao (Atmospheric Environment, 2024)

Hydrogen peroxide-induced ethylene production promotes calycosin-7-O-β-d-glucoside accumulation in Astragalus membranaceus adventitious roots - Weize Dou; Shijie Hu; Xi Lan; Mingxin Han; Xueli Quan; Songquan Wu; Jin Piao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Abnormal Changes of IL3/IL3R and Its Downstream Signaling Pathways in the Prion-Infected Cell Line and in the Brains of Scrapie-Infected Rodents - Xiao-Xi Jia; Cao Chen; Chao Hu; Zhi-Yue Chao; Wei-Wei Zhang; Yue-Zhang Wu; Qin Fan; Ru-Han A; Xin Liu; Kang Xiao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2024)

miRNAs are involved in regulating the formation of recovery tissues in virus infected Nicotiana tabacum - Jingya Zhou; Hongyan Han; Sucen Liu; Chenglong Ji; Bolei Jiao; Yiting Yang; Dehui Xi (Molecular Genetics and Genomics, 2024)

Enhancing biomass and ecological sustainability in rice–fish cocropping systems through the induction of functional microbiota with compound biogenic bait - Yang Zhang; Ying-Han Liu; Dan-Yao Tang; Jun Zhang; Xi-Yue Zhang; Chen-Wei Xu; Yu-Juan Yuan; Chuan-Chao Dai (Soil Ecology Letters, 2024)

Atmospheric Sulfur and Nitrogen Deposition in Five Nature Reserves of Sichuan Basin to Qinghai-Tibetan Plateau Transect Region, Southwestern China - Zhongjun Xu; Xi Shu; Han Yang; Liqiang Fu; Tingting Liu; Zhonglin Xia; Xue Qiao; Ya Tang (Chinese Geographical Science, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Geology and S-Pb isotope geochemistry of the Hatu gold deposit in West Junggar, NW China: Insights into ore genesis and metal source - Shen Han; Zhenju Zhou; Xiaohua Deng; Yanshuang Wu; Xi Chen; Abulimiti Aibai; Yong Wang; Xiaoyu Jia; Yanjing Chen (Acta Geochimica, 2024)

Experimental Study of Wave Load Distributions on Pile Groups Affected by Cap Structures and Pile Spacings Under Varied Wave Conditions - Wanshui Han; Kai Zhou; Jiajia Wang; Lili Xiao; Xin Xu; Yuheng Xiang; Xi Yu (Journal of Marine Science and Engineering, 2024)
Wave-induced forces pose significant challenges to marine structures, especially pile groups, where cap structures and pile spacings play critical roles in load distribution and structural stability. A physical wave flume experiment was conducted to investigate the influences of cap structures and pile spacings on wave load distributions under different wave conditions. Spatial and temporal variations in wave load distributions, including temporal variations in horizontal force, were measured as wave pressure rather than force. The results demonstrate that cap structures significantly alter the distributions of wave loads on pile groups. The integration of the cap increases the horizontal forces on the front pile and slightly reduces the vertical pressures across the pile group, particularly on the rear pile at relatively low elevations. The cap also delays the peak moment of horizontal force, especially in shallow water depths, where impact loads are more prominent and the cap induces water splash-back. Additionally, reducing pile spacing mitigates interference effects, optimizing the load distribution across piles by modulating flow velocity and pressure. The vertical pressure distribution exhibits a tiered pattern, with lower sections experiencing consistent loading, middle sections being subjected to higher loads at larger spacings, and upper sections being more affected by the cap at smaller spacings. As wave velocity and water depth increase, the differences in pressure intensity between pile groups with and without cap structures decrease, indicating the stabilizing effect of wave characteristics on structural response. This study provides insights into the design of marine pile group structures to optimize their performance characteristics under dynamic wave loading conditions.

SIRT5 safeguards against T-2 toxin induced liver injury by repressing iron accumulation, oxidative stress, and the activation of NLRP3 inflammasome - Jing Huang; Yiwen Wang; Han Hu; Kaifeng He; Xi Jiang; Rongsheng Huang; Tingting Liu; Kairao Hu; Xin Guo; Jiaxuan Wang; Dezhi Zhang; Qianyong Li; et al. (Toxicology and Applied Pharmacology, 2024)

Insight into staged gasification of biomass waste: Essential fundamentals and applications - Fang Wang; Weini Peng; Xi Zeng; Duo Sun; Guannan Cui; Zhennan Han; Chao Wang; Guangwen Xu (Science of The Total Environment, 2024)

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Physiological and transcriptomic analyses to determine the responses of the harmful algae Akashiwo sanguinea to phosphorus utilization - Han Zhang; Xi Chen; Huichen Sun; Jie Bai; Tiantian Chen (Marine Environmental Research, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Fast and accurate gas turbine emission prediction based on a light and enhanced Transformer model - Jiangjiao Li; Jin Han; Dapeng Niu; Xi Zhuo Jiang (Fuel, 2024)

Homogeneous crystallization of MA-free, wide-bandgap perovskite films via self-assembled monolayer capping for laminated silicon/perovskite tandem solar cells - Weidong Zhu; Mei Yang; Tianjiao Han; Yiru Wang; Xin Luo; Wenming Chai; He Xi; Long Zhou; Dazheng Chen; Jincheng Zhang; Chunfu Zhang; Yue Hao (Chemical Engineering Journal, 2024)

Piezoelectric-induced mechanoluminescence in centrosymmetric Lu3Al5O12: Properties of self-recoverable and tunable near-infrared luminescence - Mengjiao Li; Zhijun Wang; Xiaoshuai Zhang; Haonan Huang; Xuping Han; Xi Wang; Panlai Li (Chemical Engineering Journal, 2024)

Sequence-Unconstrained DNA Computing: DSN cycling and PER circuitry for dynamic miRNAs analysis and multifunctional logic operations - Dan Bai; Yaoyi Zhang; Jiu Pu; Li Zhang; Hongyan Yu; Xiaole Han; Ke Lv; Li Wang; Junjie Li; Ao Tang; Wang Luo; You Wu; et al. (Chemical Engineering Journal, 2024)

Strategies, techniques and applications for food authentication based on carbohydrates: A review - Li-feng Li; Xi Shi; Si-min Qi; Xue-ting Zhang; Hau-Yee Fung; Qian-ran Li; Quan-bin Han (Carbohydrate Polymers, 2024)

Effect of black soldier fly larvae frass addition on humus content during low temperature co-composting - Ruju Zhang; Yingpeng Zhang; Yonglan Xi; Jin Zhou; Ting Han; Qiuqin Ma; Cong Wang; Fei Zhu; Xiaomei Ye (Bioresource Technology, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Dose and injection site of botulinum toxin type A for gummy smile management: A systematic review and bibliometric analysis - XinYi Wang; YiRan Zou; MengNing Yuan; HongYuan Huang; XueFeng Han; Xi Gong (Toxicon, 2024)

Can ecological zoning act as an environmental management tool for protecting regional habitat quality: Causal evidence from the national key ecological function zone in China - Kai Li; XiaoLei Yan; Ying Hou; Bingyang Lv; Youyou Huang; Jing Liu; Haiting Han; Xi Li (Journal of Cleaner Production, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

A new strategy for colorimetric detection and removal of butyl xanthate in mineral processing wastewater: Based on a novel nanozyme of Ag@Fe3O4-MnO2 - Kaifeng Duan; Xin Zhao; Xi Chen; Jiangpeng Fu; Qingwei Li; Xiao Zhang; Chuanjun Zheng; Ziming Xin; Zhongtian Fu; Xiaoyu Han; Yang Wang; Cuixia Yang (Journal of Environmental Chemical Engineering, 2024)

Biotechnological approaches for targeted strain screening and enhancement of Daqu for quality baijiu production - Akhtiar Ali; Yanfang Wu; Weiwei Li; Xi Chen; Prasanna J. Patil; Meiyue Han; Haroon Shah; Lei Zhao; Xiuting Li (Food Bioscience, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

Species-level understanding of the bacterial community in Daqu based on full-length 16S rRNA gene sequences - Pei-Jie Han; Liang Song; Zhang Wen; Hai-Yan Zhu; Yu-Hua Wei; Jian-Wei Wang; Mei Bai; Lu-Jun Luo; Ju-Wei Wang; Shen-Xi Chen; Xiao-Long You; Da-Yong Han; et al. (Food Microbiology, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Hourly emission amounts and concentration of water-soluble ions in primary particles from residential coal burning in rural northern China - Qin Yan; Xi Liu; Shaofei Kong; Wenjie Zhang; Qingxian Gao; Yuzhe Zhang; Hui Li; Han Wang; Tingyu Xiao; Junhong Li (Environmental Pollution, 2024)

Quantifying the pattern of organic carbon burial through Cretaceous Oceanic Anoxic Event 2 - Huifang Guo; Xi Chen; Hanwei Yao; Yinggang Zhang; Benjamin J.W. Mills; Kaibo Han; Shujuan Wu; Yida Yang; Zihao Wang; David B. Kemp (Earth-Science Reviews, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

Extreme Wave-Induced Pressure Distribution and Wave Forces on Tandem Pile Groups: An Experimental Study - Wanshui Han; Xi Yu; Jiajia Wang; Xin Xu; Xiaokun Chen (Journal of Marine Science and Engineering, 2024)
As the foundation of marine infrastructure, pile groups are subjected to extreme wave loads. Existing research primarily focuses on regular waves and wave forces. There is limited research on the pressure distribution of pile bodies under extreme waves. This paper describes a wave flume experiment where waves of a self-proposed extreme wave type were generated. The experiment considers three water depths (25/35/45 cm), three wave-pushing velocities (20/30/40 cm/s), and two clear distances (D, 2D). A total of 216 measuring points equipped with digital pressure sensors captured the vertical and circumferential pressure distribution and wave positive force. The results show that (1) the vertical and circumferential pressure distribution patterns of each component pile and the single pile are similar in various loading scenarios and clear distances. (2) The measuring point pressure, pressure after circumferential integration, and wave positive force are positively correlated with wave-pushing velocity. (3) The wave pressure is positively correlated with the water depth, while the pressure after circumferential integration is negatively correlated with the water depth. (4) When the clear distance is D, the wave positive force coefficient of each component pile is less than 1.0.

Advanced Human Reliability Analysis Approach for Ship Convoy Operations via a Model of IDAC and DBN: A Case from Ice-Covered Waters - Yongtao Xi; Xiang Zhang; Bing Han; Yu Zhu; Cunlong Fan; Eunwoo Kim (Journal of Marine Science and Engineering, 2024)
The melting of Arctic ice has facilitated the successful navigation of merchant ships through the Arctic route, often requiring icebreakers for assistance. To reduce the risk of accidents between merchant vessels and icebreakers stemming from human errors during operations, this paper introduces an enhanced human reliability assessment approach. This method utilizes the Dynamic Bayesian Network (DBN) model, integrated with the information, decision, and action in crew context (IDAC) framework. First, a qualitative analysis of crew maneuvering behavior in scenarios involving a collision with the preceding vessel during icebreaker assistance is conducted using the IDAC model. Second, the D–S evidence theory and cloud models are integrated to process multi-source subjective data. Finally, the human error probability of crew members is quantified using the DBN. The research results indicate that during convoy operations, the maximum probability that the officer on watch (OOW) chooses an incorrect deceleration strategy is 8.259×10−2 and the collision probability is 4.129×10−3. Furthermore, this study also found that the factors of Team Effectiveness and Knowledge/Abilities during convoy operations have the greatest impact on collision occurrence. This research provides important guidance and recommendations for the safe navigation of merchant ships in the Arctic waters. By reducing human errors and adopting appropriate preventive measures, the risk of collisions between merchant ships and icebreakers can be significantly decreased.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Effects of wall confinement on flame topologies and lean blowout characteristics of partially premixed DME/air flames in a gas turbine model combustor - Xiaoxiang Shi; Zundi Liu; Tianyou Lian; Sibo Han; Yi Zhang; Zhongya Xi; Wei Li; Yuyang Li (Fuel, 2024)

Hydrogen bond regulation to promote the direct production of diosgenin from Dioscorea zingiberensis rhizomes - Yongxian Niu; Xi zhang; Wenbing Yu; Han Yin; Rui Lu; Zhenggang Liu; Fang Lu (Chemical Engineering Journal, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Biomechanical evaluation of flash-frozen and cryo-sectioned papillary muscle samples by using sinusoidal analysis: cross-bridge kinetics and the effect of partial Ca2+ activation - Jing Xi; Han-Zhong Feng; Jian-Ping Jin; Jinxiang Yuan; Masataka Kawai (Journal of Muscle Research and Cell Motility, 2024)

Unlocking the potential of surface modification with phosphate on ball milled zero-valent iron reactivity:Implications for radioactive metal ions removal - Sheng Deng; Yu Yang; Xu Han; Qiyuan Liu; Mingxiao Li; Jing Su; Yonghai Jiang; Beidou Xi; YuHui Liu (Water Research, 2024)

Histology and transcriptomic analysis reveal the inflammation and affected pathways under 2-methylisoborneol (2-MIB) exposure on grass carp - Huan Han; Jun-ming Zhang; Shuang Ji; Xiang-biao Zeng; Xi-chen Jin; Zi-qian Shen; Bin Xie; Xue-neng Luo; Kang Li; Li-ping Liu (Science of The Total Environment, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

A novel, green, and environmentally friendly PBS/nano-CaCO3 hybrid membrane - Ming Jing; Yanhong Ji; Liuchun Zheng; Xi Liu; Zunbo Han; Jiayi Cai; Rui Bai; Benqiao He (Journal of Environmental Chemical Engineering, 2024)

Integrated whole genome sequencing and transcriptomic analysis reveal the biodegradation mechanism of vanillic acid in Herbaspirillum aquaticum KLS-1 - Yong-He Han; Yi-Xi Li; Wen-Qian Qiu; Xi-Wen Cui; Xian Chen; Yong Zhang; Hong Zhang; Shan-Shan Wang (Journal of Environmental Chemical Engineering, 2024)

Unveiling the CoFe LDH generated by partial in situ conversion strategy: Synergistic effect of modified MXene and cationic vacancies for overall water splitting - Chang Xi; Wentao Ding; Jibo Jiang; Yucheng Wang; Shilong Wang; Ziyun Zhang; Sheng Han (Fuel, 2024)

Polygonum minus: A tropical medicinal herb with vast applications in food, agricultural, and medicinal fields - Zhongming Yang; Xi Deng; Zhongguo Yang; Mingzhao Han; Norsharina Ismail; Kim Wei Chan; Ahmad Faizal Abdull Razis; Norhaizan Mohd Esa; Ket Li Ho; Md Zuki Abu Bakar (Food Bioscience, 2024)

Seismic performance prediction of a slope-pile-anchor coupled reinforcement system using recurrent neural networks - Meng Wu; Xi Xu; Xu Han; Xiuli Du (Engineering Geology, 2024)

Rapid removal of uranium (VI) by phosphogypsum immobilized sulfate-reducing bacteria microspheres - Xiangyu Xi; Zhilin Wang; Lin Zhou; Han Song; Ying Han; Faqin Dong; Lei Zhou (Chemical Engineering Journal, 2024)

Are recyclable plastics eco-friendly? Recycled PVC microplastics show higher toxicity than pristine PVC on Vallisneria natans, regardless of Cadmium - Xiaohui Han; Yuxuan Gao; Li Yang; Junxin Wei; Xi Li; Lei Wang; Xinhou Zhang (Aquatic Toxicology, 2024)

Structural Characteristics and Influencing Factors of Carbon Emission Spatial Association Network: A Case Study of Yangtze River Delta City Cluster, China - Xi Bi; Renjin Sun; Dongou Hu; Hongling Shi; Han Zhang (Chinese Geographical Science, 2024)

A dried sweat spot paper (DSSP) method based on novel mass spectrometry probe labeling for detection and resolution of DL-lactate enantiomers as potential biomarkers for diabetes mellitus - Yueying Jin; Minghui Zhang; Xi-Ling Li; Chengqiang Han; Qing Shi; Jun Zhe Min (Analytica Chimica Acta, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Parental exposure to Cypermethrin causes intergenerational toxicity in zebrafish offspring - Shuang Han; Xi Liu; Yixiang Liu; Jian Lu (Science of The Total Environment, 2024)

Fabrication and characterization of alginate-zein core–shell microcapsules for controlled release of buckwheat honey - Yisu Yang; Bing Hu; Lingyu Han; Xun Zhang; Qi Wang; Chuhuan Hu; Shafi Ahmed; Koki Ryo; Xi Yang (Food Chemistry, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

A new biphenanthrene with cytotoxic activity from Liparis nervosa (Thunb.) Lindl - Liang Liu; Qi-Meng Yin; Qi-Jun Dai; Xuan-Yuan Chen; Xi-Qing Chen; Jian-Bin Wang; Han-Qing Pang; Xian-Wen Zhang (Natural Product Research, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Insights into the effect of guanylate-binding protein 1 on the survival of Brucella intracellularly - Zhiqiang Li; Shuli Wang; Jincheng Han; Guangli Yang; Li Xi; Chunmei Zhang; Yanyan Cui; Shuanghong Yin; Yu Zhang; Hui Zhang (Veterinary Microbiology, 2024)

Fine particulate matter exposure and systemic inflammation: A potential mediating role of bioactive lipids - Wu Chen; Yiqun Han; Yifan Xu; Teng Wang; Yanwen Wang; Xi Chen; Xinghua Qiu; Weiju Li; Haonan Li; Yunfei Fan; Yuan Yao; Tong Zhu (Science of The Total Environment, 2024)

Characteristics of number concentration, size distribution and components of particulate matter emitted from a typical large civil airport - Sihan Yin; Zhichao Lu; Yufei Zhang; Lilai Song; Shenyu Bi; Xi Luo; Lu Yao; Xiaohui Bi; Han Bo; Yinchang Feng (Science of The Total Environment, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Anthropogenic gadolinium sources and remediation in highly urbanized river in the Beijing-Tianjin-Hebei (BTH) region, China: Insights from buffer zone and three-dimensional tracer system - Xi Gao; Guilin Han; Shitong Zhang; Jinke Liu; Di Wang; Shunrong Ma; Yuqing Zhao (Process Safety and Environmental Protection, 2024)

Toxin production and transcriptomic response to nitrate concentrations in the toxic dinoflagellate Alexandrium tamarense - Tiantian Chen; Han Zhang; Wenlong Dong; Kexin Bu; Xi Chen (Marine Environmental Research, 2024)

Emission of CO2 and its related carbonate system dynamics in a hotspot area during winter and summer: The Changjiang River estuary - Bing-Han Li; Hai-Long Zhao; Jiang-Chen Gong; Xi Wu; Chun-Ying Liu; Jing-Wen Hu; Gui-Peng Yang (Marine Environmental Research, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Co-migration behavior of toluene coupled with trichloroethylene and the response of the pristine groundwater ecosystems – A mesoscale indoor experiment - Shuxuan Wu; Yu Yang; Zhifei Ma; Fan Feng; Xiangjian Xu; Sheng Deng; Xu Han; Beidou Xi; Yonghai Jiang (Journal of Hazardous Materials, 2024)

Satellite mapping reveals phytoplankton biomass's spatio-temporal dynamics and responses to environmental factors in a eutrophic inland lake - Lai Lai; Yuchao Zhang; Tao Han; Min Zhang; Zhen Cao; Zhaomin Liu; Qiduo Yang; Xi Chen (Journal of Environmental Management, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

The association between brominated flame retardants exposure with bone mineral density in US adults: A cross-sectional study of the national health and nutrition examination survey (NHANES) 2005–2014 - Tianyu Bai; Xiangjun Li; Han Zhang; Wenkang Yang; Changlin Lv; Xiaofan Du; Shiqi Xu; Aiping Zhao; Yongming Xi (Environmental Research, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

A functional study reveals CsNAC086 regulated the biosynthesis of flavonols in Camellia sinensis - Sa-Sa Song; Wei-Xi Ran; Long-Han Gao; Yu-Chun Wang; Wu-Yun Lv; Yu Tao; Liang Chen; Chun-Fang Li (Planta, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

An Improved Faster R-CNN Method for Landslide Detection in Remote Sensing Images - Han Qin; Jizhou Wang; Xi Mao; Zhan’ao Zhao; Xuanyu Gao; Wenjuan Lu (Journal of Geovisualization and Spatial Analysis, 2024)

Arsenic uptake and biotransformation mechanisms in Dunaliella salina: Insights into physiological and molecular responses - Yimei Xi; Bolei Han; Zefang Meng; Yongbin Li; Xiangfeng Zeng; Fantao Kong; Tingting You; Ran Bi; Shaofeng Wang; Yongfeng Jia (Algal Research, 2024)

Corrigendum to “Urinary biomarkers of exposure to organophosphate, pyrethroid, neonicotinoid insecticides and oxidative stress: A repeated measurement analysis among pregnant women” [Sci. Total Environ. volume 912, 2024, 169565] - Aizhen Wang; Yanjian Wan; Wei Qi; Gaga Mahai; Xi Qian; Tongzhang Zheng; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Science of The Total Environment, 2024)

Arsenic-enhanced plant growth in As-hyperaccumulator Pteris vittata: Metabolomic investigations and molecular mechanisms - Yong-He Han; Yi-Xi Li; Xian Chen; Hong Zhang; Yong Zhang; Wei Li; Chen-Jing Liu; Yanshan Chen; Lena Q. Ma (Science of The Total Environment, 2024)

Release kinetics and risk assessment of additives in plastic advertising banners - Xi Chen; Wenjing Han; Huaijun Xie; Jingwen Chen (Science of The Total Environment, 2024)

Unlocking sustainable resource management: A comprehensive SWOT and thematic analysis of FinTech with a focus on mineral management - Mehrbakhsh Nilashi; Rabab Ali Abumalloh; Ooi Keng-Boon; Garry Wei-Han Tan; Tat-Huei Cham; Eugene Cheng-Xi Aw (Resources Policy, 2024)

Bioinsecticide PA1b alleviates lipopolysaccharide-induced inflammation and impairment of bovine mammary epithelial cells - Peng Dan; Han Zhao; Jiahui Xi; Yanying Zhao (Pesticide Biochemistry and Physiology, 2024)

A green, efficient, and degradable poly(butylene succinate) (PBS)/TiO2 hybrid membrane for water treatment - Xi Liu; Yanhong Ji; Yinjie Sun; Ming Jing; Zunbo Han; Yunfei Song; Yangzhen Liu; Haoran Chen; Benqiao He (Journal of Water Process Engineering, 2024)

Advancing microplastic surveillance through photoacoustic imaging and deep learning techniques - Mengyuan Huang; Kaitai Han; Wu Liu; Zijun Wang; Xi Liu; Qianjin Guo (Journal of Hazardous Materials, 2024)

Two-stage fluidized bed gasification enhanced with oxidative pyrolysis for low-tar producer gas from biomass - Chao Wang; Fangzheng Liu; Lianfeng Zhu; Xinyu Wang; Cong Zhang; Mengjuan Zhang; Zhennan Han; Xin Jia; Guoqing Guan; Xi Zeng; Fang Wang; Guangwen Xu (Fuel, 2024)

Amino acid carbon isotope profiles provide insight into lability and origins of particulate organic matter - Peihong Kang; Lingyu Ma; Han Zhang; Xi Dai; Jie Liu; Weifang Chen; Tiantian Tang (Limnology and Oceanography, 2024)
Identifying the phytoplankton origin of particulate organic matter (POM) in the deep ocean is challenging due to the changing phytoplankton composition and varied extent of decomposition by heterotrophic bacteria and zooplankton. Here, we report vertical distributions of amino acid stable carbon isotope values (δ 13 C) measured in particles in the South China Sea. Carbon‐weighted amino acid δ 13 C values generally parallel bulk POM δ 13 C profiles with a positive offset from 2.4‰ in the surface water to 6.0‰ in deep. Accordingly, a lability model is introduced to describe the relative distribution and isotopic linkage of labile and refractory particulate organic carbon. Temporal changes of amino acid δ 13 C were observed during the microbial decomposition of two phytoplankton strains, the prokaryote cyanobacterium Synechococcus and the eukaryote diatom Thalassiosira weissflogii . Principal component analysis of individual amino acid δ 13 C values from the decomposing cells separate samples into two components, reflecting the influence of microbial decomposition and taxonomic differences, respectively. These two components were further applied to particles. A major contribution from decomposing phytoplankton to particles below the euphotic zone was observed, with more prokaryote organic matter in the basin and a larger contribution from eukaryotes at stations near the productive northern shelf. Our findings show the applicability of amino acid δ 13 C values in tracing the lability and phytoplankton origins of POM in samples with varied extents of decomposition in marine environments.

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Unveiling the activation mechanism: The role of nitrogen-doped biochar in enhancing Fe(VI) catalysis - Sheng Deng; Xu Han; Ningqing Lv; Xiaochun Yang; Qiyuan Liu; Yonghai Jiang; Yu Yang; Beidou Xi (Chemical Engineering Journal, 2024)

Novel Aliphatic polycarbonate binders for Solvent‑free manufacturing High‑loading cathodes of high-performance lithium-ion batteries - Guan Xi; Zhe Zhang; Lei Zhong; Shuanjin Wang; Min Xiao; Dongmei Han; Sheng Huang; Yuezhong Meng (Chemical Engineering Journal, 2024)

Research on CO2 capture performance and reaction mechanism using newly tetraethylenepentamine (TEPA) + monoethanolamine (MEA) mixed absorbent for onboard application - Song Zhou; Yunlong Zhu; Hongyuan Xi; Ze Hao; Zhitao Han; Chengqi Sun (Chemical Engineering Journal, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

The pig intestinal phageome is an important reservoir and transfer vector for virulence genes - Yalu Ji; Hengyu Xi; Chong Chen; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; Jingmin Gu (Science of The Total Environment, 2024)

Performance assessment of solar photovoltaic-based constructed wetland for sustainable rural wastewater treatment - Ye Yang; Chao-Kun Li; Liu Han; Zhi-Peng Yang; Ning-Ning Xiao; Nan Zhang; Ying-Ying Dong; Zhi-Wen Chen; Hui Xi; Wen-Dong Wang (Journal of Water Process Engineering, 2024)

Nature, source, and evolution of the ore-forming fluids in the Dunbasitao gold deposit, East Junggar, China: Constraints from geology, fluid inclusions, and C-H-O isotopes - Wenxiang Liu; Xiaohua Deng; Franco Pirajno; Shen Han; Xi Chen; Xun Li; Abulimiti Aibai; Yanshuang Wu; Yong Wang; Yanjing Chen (Journal of Geochemical Exploration, 2024)

Composition and release rates of chemicals in inkjet fabrics determined by non-targeted screening and targeted analysis - Xi Chen; Wenjing Han; Jingwen Chen; Huaijun Xie; Qing Xie; Minghua Zhu; Zhongyu Wang; Yunhan Cui; Weihao Tang (Environmental Pollution, 2024)

Bio-adhesive barrier with active ROS-scavenging ability for simultaneous management of dura tear and epidural inflammatory fibrosis - Meng Han; Jincheng Tang; Haiyue Zhao; Yachao Sheng; Ziang Li; Wenxiao Shi; Jiahao Wang; Chao Ma; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2024)

Single-cell transcriptomic analysis reveals transcriptional and cell subpopulation differences between human and pig immune cells - Jie Li; Yanan Xu; Jiayu Zhang; Zhaoqi Zhang; Han Guo; Dong Wei; Changhong Wu; Tang Hai; Hai-Xi Sun; Yong Zhao (Genes & Genomics, 2024)

Research on the characteristics of total-field data converted from aeromagnetic vertical gradient data based on a continuation conversion filtering algorithm - Hua Guo; Xi Xu; Song Han; Qiang Zheng; Haojun Liu (Applied Geophysics, 2024)

Distribution patterns and influential factors of pathogenic bacteria in freshwater aquaculture sediments - Wenxiang Xi; Xun Zhang; Xianbin Zhu; Jiaming Wang; Han Xue; Hongzhong Pan (Environmental Science and Pollution Research, 2024)

Analysis of environmental biological effects and OBT accumulation potential of microalgae in freshwater systems exposed to tritium pollution - Jin-long Lai; Zhan-guo Li; Meng-wei Han; Yan Huang; Hai-ling Xi; Xue-gang Luo (Water Research, 2024)

Urinary biomarkers of exposure to organophosphate, pyrethroid, neonicotinoid insecticides and oxidative stress: A repeated measurement analysis among pregnant women - Aizhen Wang; Yanjian Wan; Wei Qi; Gaga Mahai; Xi Qian; Tongzhang Zheng; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Science of The Total Environment, 2024)

Unveiling the responses of Alexandrium pacificum to phosphorus utilization by physiological and transcriptomic analysis - Tiantian Chen; Xi Chen; Huichen Sun; Han Zhang; Jie Bai (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Fine-tuning bromide AIE probes for Hg2+ detection in mitochondria with wash-free staining - Tian Tan; Chuang Zhang; Ying Han; Ruijun Chu; Wenyu Xi; Xulang Chen; Jingyu Sun; Hong Huang; Yanjun Hu; Xiaohuan Huang (Journal of Hazardous Materials, 2024)

Plastic protective nets: A significant but neglected “reservoir” for priority chemicals as revealed by composition analysis - Wenjing Han; Zhongyu Wang; Qing Xie; Xi Chen; Lihao Su; Huaijun Xie; Jingwen Chen; Zhiqiang Fu (Journal of Hazardous Materials, 2024)

Estimating fossil CO2 emissions from COVID-19 post-pandemic recovery in G20: A machine learning approach - Shiyu Deng; Xi Deng; Han Chen; Zhangcai Qin (Journal of Cleaner Production, 2024)

An improved re-entrant honeycomb with programmable densification and multistage energy-absorbing performance - Wei Zhong Jiang; Xing Chi Teng; Xi Hai Ni; Xue Gang Zhang; Xian Cheng; Wei Jiang; Dong Han; Yi Zhang; Xin Ren (Engineering Structures, 2024)

Dual biomimetic surfaces with anisotropic wettability for multi-scale droplets manipulation - Hanpeng Gao; Haoyang Zhao; Jiaxi Liu; Yan Liu; Zong Meng; Yunyun Song; Xi Wang; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2024)

Moderate salt spraying on grapevine canopy induces differential modulation of anthocyanin synthesis profiles during early and late stages of berry ripening in Cabernet Sauvignon - Ning Han; Lanxin Li; Fengjie Wang; Zhen Yang; Xi He (Horticulture, Environment, and Biotechnology, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Circ_0059457 Promotes Proliferation, Metastasis, Sphere Formation and Glycolysis in Breast Cancer Cells by Sponging miR-140-3p to Regulate UBE2C - Li Huang; Guochen Zhang; Lei Han; Xiangdong Bai; Zhibin Xi; Fan Wang; Guohui Han (Biochemical Genetics, 2024)

Frequency-specific functional difference between gyri and sulci in naturalistic paradigm fMRI - Liting Wang; Yang Yang; Xintao Hu; Shijie Zhao; Xi Jiang; Lei Guo; Junwei Han; Tianming Liu (Brain Structure and Function, 2024)

Investigation of ash fusion characteristics on co-combustion of coal and biomass (straw, sludge, and herb residue) based on experimental and machine learning method - Ming Lei; Hui Han; Xi Tian; Lei Zhang; Qian Zhang (Environmental Science and Pollution Research, 2024)

Constructing carbon-based materials loaded with MOFs to realize efficient anaerobic digestion of rural organic waste - Xiaomei Ye; Zhaoyan Jia; Yang Liu; Chengcheng Wang; Chunhui Cao; Yingpeng Zhang; Ting Han; Li Wang; Ting Guo; Yonglan Xi (Fuel, 2024)

RETRACTED: Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2024)

Eliminating concentration polarization with gradient lithiophilic sites towards high performance lithium metal anodes under low N/P ratio - Zichun Xiao; Duzhao Han; Yu Fu; Keyu Xie; Wensheng Tian; Chengyong Shu; Kai Xi; Chengxin Peng; Yuping Wu; Shixue Dou; Wei Tang (Chemical Engineering Journal, 2024)

Water-assisted mass preparation of CsPbBr3-CsPb2Br5-CsPbIxBr3-x composite wafers for high-performance X-ray detection - Yanshuang Ba; Yaoyu Han; Weidong Zhu; Tianran Wang; Jiawei Chi; He Xi; Tianlong Zhao; Dazheng Chen; Jincheng Zhang; Chunfu Zhang; Yue Hao (Chemical Engineering Journal, 2024)

Cyclophosphamide reduces gene transcriptional activity and embryo in vitro development by inhibiting NF-κB expression through decreasing AcH4K12 - Zhao-Bo Luo; Liu-Hui Yang; Sheng-Zhong Han; Shuang-Yan Chang; Hongye Liu; Zhi-Yong An; Xiu-Li Zhang; Biao-Hu Quan; Xi-Jun Yin; Jin-Dan Kang (Chemico-Biological Interactions, 2024)

The spatiotemporal variability in precipitation gradients based on meteorological station observations in mountainous areas of Northwest China - Xi Zhang; Min Xu; Shichang Kang; Hao Wu; Haidong Han (Theoretical and Applied Climatology, 2024)

Climate match is key to predict range expansion of the world's worst invasive terrestrial vertebrates - Yuanbao Du; Xuyu Wang; Sadia Ashraf; Weishan Tu; Yonghong Xi; Ruina Cui; Shengnan Chen; Jiajie Yu; Lixia Han; Shimin Gu; Yanhua Qu; Xuan Liu (Global Change Biology, 2024)
Understanding the determinants of the range expansion of invasive alien species is crucial for developing effective prevention and control strategies. Nevertheless, we still lack a global picture of the potential factors influencing the invaded range expansion across taxonomic groups, especially for the world's worst invaders with high ecological and economic impacts. Here, by extensively collecting data on 363 distributional ranges of 19 of world's worst invasive terrestrial vertebrates across 135 invaded administrative jurisdictions, we observed remarkable variations in the range expansion across species and taxonomic groups. After controlling for taxonomic and geographic pseudoreplicates, model averaging analyses based on generalized additive mixed‐effect models showed that species in invaded regions having climates more similar to those of their native ranges tended to undergo a larger range expansion. In addition, as proxies of propagule pressure and human‐assisted transportation, the number of introduction events and the road network density were also important predictors facilitating the range expansion. Further variance partitioning analyses validated the predominant role of climate match in explaining the range expansion. Our study demonstrated that regions with similar climates to their native ranges could still be prioritized to prevent the spread of invasive species under the sustained global change.

Combined application of nitrogen, phosphorus, iron, and silicon improves growth and fatty acid composition in marine epiphytic diatoms - Miao Yang; Xin-Yue Xu; Han-Wen Hu; Wei-Dong Zhang; Jing-Yi Ma; Heng-Ping Lei; Qing-Zhi Wang; Xi Xie; Zheng Gong (Frontiers in Marine Science, 2023)
Introduction Marine epiphytic diatoms are natural diets for multiple marine invertebrates, including sea cucumbers, sea urchins, etc. They also act as bioindicators in marine waters to assess water quality of coastal ecosystems. Material and methods We isolated three strains of Navicula and two strains of Nitzschia from macroalgal epiphytes. Combined concentrations of four macroelements, five trace metals, and three vitamins in f/2 medium were optimized for these diatoms using single-factor and orthogonal tests. Results and discussion The biomass productivities for 4-L enlarged cultures of the five isolated diatoms in their exclusively optimized f/2 media all increased by nearly 10-fold relative to f/2 medium, and that of Navicula -1 and Nitzschia -2 reached the highest, i.e., 29.52 ± 1.98 and 30.68 ± 2.84 g m -2 d -1 , respectively. Moreover, the relative abundance of C20:5n3 in the exclusively optimized f/2 medium-cultured Navicula -1 notably rose by 24%, and that in Nitzschia -2 held stable at > 25%. Thus, Navicula -1 and Nitzschia -2 were screened out with outstanding growth traits and improved fatty acid compositions at high levels of combined nitrogen, phosphorus, iron, and silicon. The two diatoms have potential for becoming quality diets for marine aquaculture, and ideal candidates for effective nutrient removal.

Physiological tolerance of black locust (Robinia pseudoacacia L.) and changes of rhizospheric bacterial communities in response to Cd and Pb in the contaminated soil - Xu-Feng Luo; Meng-Yu Liu; Zi-Xi Tian; Yue Xiao; Peng Zeng; Zi-Yu Han; Hang Zhou; Jiao-Feng Gu; Bo-Han Liao (Environmental Science and Pollution Research, 2023)

Progress in phytoremediation of chromium from the environment - Lingzhuo Han; Haiping Gu; Wenjie Lu; Hanyin Li; Wan-xi Peng; Nyuk Ling Ma; Su Shiung Lam; Christian Sonne (Chemosphere, 2023)

The protective immunity induced by Trichinella spiralis galectin against larval challenge and the potential of galactomannan as a novel adjuvant - Ru Zhang; Xin Zhuo Zhang; Xin Guo; Lu Lu Han; Bo Ning Wang; Xi Zhang; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (Research in Veterinary Science, 2023)

Inactivation of Staphylococcus aureus in water by dielectric barrier discharge plasma jet: The role of inorganic ions, organic matter, and turbidity - Zimu Xu; Yandan Tang; Shuheng Hu; Yan Lan; Wenhao Xi; Wei Han; Danzhou Wu; Fan Yang; Cheng Cheng (Journal of Water Process Engineering, 2023)

Effect of damming on hydrogeochemical characteristics and potential environmental risks in a large reservoir: Insights from different vertical layer sampling - Di Wang; Guilin Han; Mingming Hu; Yuchun Wang; Jinke Liu; Xi Gao (Environmental Research, 2023)

Tidal effects on carbon dioxide emission dynamics in intertidal wetland sediments - Jiang-Chen Gong; Bing-Han Li; Jing-Wen Hu; Xi-Ju Ding; Chun-Ying Liu; Gui-Peng Yang (Environmental Research, 2023)

Ultrathin 3D CoMn nanoflowers coupled diatomite for highly efficient catalytic oxidation of CO and propane - Qinghe Liu; Meng Li; Sen Wang; Shupei Lv; Fei Han; Yunfei Xi; Zhou Cao; Jing Ouyang (Chemical Engineering Journal, 2023)

Long-term impacts of extensive terracing on soil aggregates and associated C–N–P in the Camellia oleifera orchard of southern China - Han Zheng; Xi Wang; Jin Wu; Wenqing Li; Changyin Tan; Yuan Chen; Feng Zhang; Jian Duan; Zhongwu Li; Yaojun Liu (CATENA, 2023)

Key decomposers of straw depending on tillage and fertilization - Hao Xi; Mengying Jia; Yakov Kuzyakov; Zhenling Peng; Yali Zhang; Jiayao Han; Gohar Ali; Lin Mao; Jianjun Zhang; Tinglu Fan; Yongjun Liu (Agriculture, Ecosystems & Environment, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Exposure to phthalates and their alternatives in relation to biomarkers of inflammation and oxidative stress in adults: evidence from NHANES 2017–2018 - Shihao Jin; Shanshan Cui; Xiaoyu Mu; Zhao Liu; Yu Han; Tingkai Cui; Wenjuan Xiong; Wei Xi; Xin Zhang (Environmental Science and Pollution Research, 2023)

Critical review on modified floating photocatalysts for emerging contaminants removal from landscape water: problems, methods and mechanism - Xiaoning Fu; Guangzhu Zhou; Jianping Li; Qiuhui Yao; Zuozhen Han; Rongchao Yang; Xi Chen; Yuanhao Wang (Chemosphere, 2023)

Insights into the response of anammox process to oxytetracycline: Impacts of static magnetic field - Qian Wang; Xiaoyi Sun; Wenli Fan; Xi Chen; Wenxuan Han; Shuang Zhao; Wenlin Jia (Chemosphere, 2023)

Construction of an Early Cambrian intra-oceanic arc within the West Junggar, NW China: Magmatic records from proto- to mature-arc - Qi-Song Luo; Zheng-Yu Yang; Xiao-Han Gong; Ji-Feng Xu; Xi-Jun Liu; Peng-Yu He; Zhi-Guo Zhang (Lithos, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

The new strategy of using humic acid loaded biochar to enhance the anaerobic digestion of cow manure for methane production - Yang Liu; Jing Du; Xiaomei Ye; Kequan Chen; Qingbo Xiao; Zhiyang Zhang; Chunhui Cao; Ting Han; Xiangping Kong; Yonglan Xi (Journal of Cleaner Production, 2023)

Determination of multiclass contaminants in chilli powder based on magnetic multiwalled carbon nanotubes and UPLC-QTOF/MS - Guangyun He; Xue Hou; Mei Han; Shiting Qiu; Xi Yu; Shudi Qin; Fengyi Wang; Ying Li (Food Research International, 2023)

3D-exosomes laden multifunctional hydrogel enhances diabetic wound healing via accelerated angiogenesis - Han Peng; Huichen Li; Xi Zhang; Jiezhang Tang; Yongping Liang; Lipeng Qiao; Yun Zhu; Mengmeng Hou; Siming Wei; Zhaoxiang Zhang; Chaohua Liu; Xinmao Li; et al. (Chemical Engineering Journal, 2023)

Effect and mechanism of a concentration-dependent inorganic ion biomimetic periosteum in a repairing bone defect - Lichen Zhang; Jincheng Tang; Meng Han; Yang Sun; Wei Wang; Zhuojun Wu; Yachao Sheng; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2023)

Low-δ56Fe fluid released from serpentinite as recorded by iron isotopes of Myanmar jadeitites - An-Xia Chen; Xi Chen; Yi Chen; Xi-Qiu Han; Ye-Jian Wang; Fang Huang (Chemical Geology, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Maize, wheat, and soybean root traits depend upon soil phosphorus fertility and mycorrhizal status - Jiayao Han; Yali Zhang; Hao Xi; Jing Zeng; Zhenling Peng; Gohar Ali; Yongjun Liu (Mycorrhiza, 2023)

Butachlor (BTR) degradation by dielectric barrier discharge plasma in soil: Affecting factors, degradation route, and toxicity assessment - Shuheng Hu; Xin Jin; Xueyan Chen; Bin Lv; Wenhao Xi; Yan Lan; Wei Han; Zimu Xu; Cheng Cheng (Chemosphere, 2023)

Collaborative path planning and task allocation for multiple agricultural machines - Ning Wang; Xi Yang; Tianhai Wang; Jianxing Xiao; Man Zhang; Hao Wang; Han Li (Computers and Electronics in Agriculture, 2023)

The urbanization impacts on potentially toxic metals: the distribution, sources and contamination risks in river situated in typical megacity, China - Shitong Zhang; Guilin Han; Xi Gao (Sustainable Cities and Society, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Research on dynamic p-y curves in liquefied sand under cyclic loading conditions - Xiao-ling Zhang; Bing-jie Zhang; Wen-Xi Zhang; Yan Han (Ocean Engineering, 2023)

Enhancement of arsenic uptake and accumulation in green microalga Chlamydomonas reinhardtii through heterologous expression of the phosphate transporter DsPht1 - Yimei Xi; Bolei Han; Fantao Kong; Tingting You; Ran Bi; Xiangfeng Zeng; Shaofeng Wang; Yongfeng Jia (Journal of Hazardous Materials, 2023)

Enhanced degradation of tetracycline hydrochloride with in situ prepared ferrate supernatant based on calcium hypochlorite: Compare with purified and commercial ferrate - Xiaochun Yang; Yu Yang; Xu Han; Yonghai Jiang; Beidou Xi; Han Xiao; Xiangjian Xu; Yuhan Hu; Sheng Deng; Jiao Zhang (Journal of Environmental Chemical Engineering, 2023)

Controlling microbial population in livestock and poultry industry using electrolyzed water as an emerging technology for ensuring food safety - Syed Md. Ehsanur Rahman; Sarder Md. Ariful Islam; Dewei Kong; Qian Xi; Qijing Du; Yongxin Yang; Deog-Hwan Oh; Jun Wang; Rongwei Han (Food Control, 2023)

Surrogate modeling and global sensitivity analysis for the simultaneous growth of multiple hydraulic fractures - Shaoyi Cheng; Bisheng Wu; Ming Zhang; Xi Zhang; Yanhui Han; Robert G. Jeffrey (Computers and Geotechnics, 2023)

Ascendant bioinspired emulsion separation materials: From the perspective of droplet movement - Hanpeng Gao; Siyu Chang; Jiaxi Liu; Yan Liu; Zong Meng; Yunyun Song; Xi Wang; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2023)

Study on the effective removal of chlorpyrifos from water by dielectric barrier discharge (DBD) plasma: The influence of reactive species and different water components - Zimu Xu; Xueyan Chen; Xin Jin; Shuheng Hu; Yan Lan; Wenhao Xi; Wei Han; Cheng Cheng (Chemical Engineering Journal, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

Modeling of breaching parameters for debris flow dams - He-chun Ruan; Hua-yong Chen; Xiao-qing Chen; Wan-yu Zhao; Jian-gang Chen; Tao Wang; Yao Jiang; Xi-an Wang; Xiang-ning Li; Xiao Li; Yun-han Yu (Journal of Mountain Science, 2023)

Binocular Vision-Based Non-Singular Fast Terminal Control for the UVMS Small Target Grasp - Tao Jiang; Yize Sun; Hai Huang; Hongde Qin; Xi Chen; Lingyu Li; Zongyu Zhang; Xinyue Han (Journal of Marine Science and Engineering, 2023)
Autonomous underwater manipulation is very important for the robotic and intelligence operations of oceanic engineering. However, a small target often involves limited features and results in inaccurate visual matching. In order to improve visual measurement accuracy, this paper has proposed an improved unsharp masking algorithm to further enhance the weak texture region of blurred and low contrast images. Moreover, an improved ORB feature-matching method with adaptive threshold, non-maximum suppression and improved random sample consensus has also been proposed. To overcome unknown underwater disturbances and uncertain system parameters in the underwater robotic manipulations, an adaptive non-singular terminal sliding mode controller has been proposed with a quasi-barrier function to suppress the chattering problem and improve grasp accuracy for small target. Oceanic experiments have been conducted to prove the performance of the proposed method.

Exopolysaccharides synthesized by lactic acid bacteria: biosynthesis pathway, structure-function relationship, structural modification and applicability - Jinsong Wu; Xiangpeng Han; Meizhi Ye; Yao Li; Xi Wang; Qingping Zhong (Critical Reviews in Food Science and Nutrition, 2023)

New furofuran and tetrahydrofuran lignans from the flower buds of Magnolia biondii Pamp and their antiallergic effects - Xing Zhang; Xi-Min Wu; Lin-Hang Han; Fei Qian; Liu-Qiang Zhang; Yi-Ming Li (Natural Product Research, 2023)

Room temperature removal of high-space-velocity formaldehyde boosted by fixing Pt nanoparticles into Beta zeolite framework - Xiaoling Liu; Yitong Liu; Yue Wu; Shan Dong; Guoqin Qi; Cailing Chen; Shibo Xi; Pan Luo; Yihu Dai; Yu Han; Yu Zhou; Yu Guo; et al. (Journal of Hazardous Materials, 2023)

How can greenery space mitigate urban heat island? An analysis of cooling effect, carbon sequestration, and nurturing cost at the street scale - Chang Xi; Li Han; Junqi Wang; Zhuangbo Feng; Prashant Kumar; Shi-Jie Cao (Journal of Cleaner Production, 2023)

Paleo-Asian oceanic crust trapped by irregular continental margin contributes to continental growth: Evidence from airborne gravity and magnetic imaging across the Alxa tectonic belt, Central Asia - Xingtao Kuang; Xi Xu; Hongwei Duan; Baobao Cao; Fangxin Ning; Mengchu Xiao; Song Han; Daoqing Zhou; Baodi Wang (Gondwana Research, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Biodegradation of p-hydroxybenzoic acid in Herbaspirillum aquaticum KLS-1 isolated from tailing soil: Characterization and molecular mechanism - Yi-Xi Li; Wei Lin; Yong-He Han; Yao-Qiang Wang; Tao Wang; Hong Zhang; Yong Zhang; Shan-Shan Wang (Journal of Hazardous Materials, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Simultaneous removal of antibiotic-resistant Escherichia coli and its resistance genes by dielectric barrier discharge plasma - Shuheng Hu; Yuhang Fu; Muen Xue; Yan Lan; Wenhao Xi; Zimu Xu; Wei Han; Danzhou Wu; Cheng Cheng (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Targeting Peripheral μ-opioid Receptors or μ-opioid Receptor-Expressing Neurons Does not Prevent Morphine-induced Mechanical Allodynia and Anti-allodynic Tolerance - Feng Du; Guangjuan Yin; Lei Han; Xi Liu; Dong Dong; Kaifang Duan; Jiantao Huo; Yanyan Sun; Longzhen Cheng (Neuroscience Bulletin, 2023)

3-Methyladenine ameliorates surgery-induced anxiety-like behaviors in aged mice by inhibiting autophagy-induced excessive oxidative stress - Song-Tao Wu; Shan-Shan Han; Xi-Ming Xu; Hai-Jun Sun; Hua Zhou; Kun Shang; Zi-Hao Liu; Shu-Juan Liang (Metabolic Brain Disease, 2023)

FDX1 enhances endometriosis cell cuproptosis via G6PD-mediated redox homeostasis - Jiayi Lu; Xi Ling; Yonghong Sun; Lu Liu; Lan Liu; Xiaoyun Wang; Chao Lu; Chune Ren; Xue Han; Zhenhai Yu (Apoptosis, 2023)

A comprehensive performance evaluation methodology for sea-crossing cable-stayed bridges under wind and wave loads - Chao Li; Guo-Yi Wu; Lu-Xi Li; Chun-Guang Liu; Hong-Nan Li; Qiang Han (Ocean Engineering, 2023)

A review on risk assessment methods for maritime transport - Xi Huang; Yuanqiao Wen; Fan Zhang; Haihang Han; Yamin Huang; Zhongyi Sui (Ocean Engineering, 2023)

Evidence of deep fluid activity in Jurassic tight sandstone reservoirs in the Northern Kuqa Depression - Yifan Zhang; Kelai Xi; Yingchang Cao; Xianzhang Yang; Zhenping Xu; Lu Zhou; Guoding Yu; Zhanghua Han; Zehan Zhang (Marine and Petroleum Geology, 2023)

Early Cambrian oceanic crust in the Chinese North Tianshan: Evidence of the earliest subduction system within the southwestern Central Asian Orogenic Belt - Zheng-Yu Yang; Qi-Song Luo; Xiao-Han Gong; Ji-Feng Xu; Xi-Jun Liu; Peng-Yu He; Zhi-Guo Zhang (Gondwana Research, 2023)

Exploration on laminar flame propagation of biogas and DME mixtures up to 10 atm: Insight into effects of DME co-firing, CO2 addition and pressure - Zhongya Xi; Jianguo Zhang; Wei Li; Zundi Liu; Xiaoxiang Shi; Tianyou Lian; Sibo Han; Yuyang Li (Fuel, 2023)

Mixed exposure effect of seminal metals on semen quality, mediation of total antioxidant capacity, and moderation of GSTM1/GSTT1 gene deletion in Chinese reproductive-aged men - Jingchao Ren; Huidong Jin; Chen Zhang; Song Liu; Yufen Han; Jinyan Xi; Jinhu Cao; Fenglong Lin; Pingyang Zhang; Fengquan Zhang; Guang-hui Zhang; Huijun Yang; et al. (Environmental Research, 2023)

Ecohydraulic modelling to evaluate cascade dam construction impact and support fish habitat restoration - Qianqian Wang; Yu Han; Pengcheng Li; Wenming Zhang; Yihang Wang; Yuqian Xi; Weiwei Yao (Ecological Engineering, 2023)

Molecular detection and genetic characteristics of a novel porcine circovirus (porcine circovirus 4) and porcine reproductive and respiratory syndrome virus in Shaanxi and Henan Provinces of China - Xi-Meng Chen; You-Yi Zhao; Xiao-Chen Liu; Ying-Ying Han; Yuan-Hang Zhang; Cheng-Yao Hou; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Stable isotope labeling differential glycans discovery in the serum of acute myocardial infarction by ultrahigh-performance liquid chromatography-quadrupole-Orbitrap high resolution mass spectrometry - Xi-Ling Li; Yuxuan Li; Shuyun Xiao; Qingsong Li; Chengqiang Han; Danyang Liu; Tengfei Cui; Xiyang Rao; Kenichiro Todoroki; Guang Yang; Jun Zhe Min (Analytica Chimica Acta, 2023)

Geochronology and petrogenesis of the Yeba formation volcanic rocks in the Epingsong area, southern Lhasa terrane, Tibet: record of the Neo-Tethys subduction - Peng Fan; Bin Zhou; Aihua Xi; Xinxing Qiao; Liang Pan; Kui Han; Xu Chao; Wenbo Yang; Zhongshan Wu (International Geology Review, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Arsenic triggered nano-sized uranyl arsenate precipitation on the surface of Kocuria rosea - Lei Zhou; Faqin Dong; Xiangyu Xi; Lin Zhou; Qunwei Dai; Mingxue Liu; Ying Han; Gang Yang; Yongde Zhang (Journal of Environmental Radioactivity, 2023)

Synthesis of Co(OH)F@Al nanobelt array on various substrates for pyro-MEMS - Yuxiang Li; Xi Chen; Lei Zhang; Ruishan Han; Iftikhar Hussain; Xiaoxia Ma; Kaili Zhang (Chemical Engineering Journal, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Complex vegetation patterns improve soil nutrients and maintain stoichiometric balance of terrace wall aggregates over long periods of vegetation recovery - Wenqing Li; Yaojun Liu; Han Zheng; Jin Wu; Haiqun Yuan; Xi Wang; Wenbin Xie; Yue Qin; Huade Zhu; Xiaodong Nie; Zhongwu Li (CATENA, 2023)

GSH-Dependent PTMs of Proteins Differ Significantly Between Ontogenetic Phases of Apple Trees - Jing Yang; Qingbo Zheng; Yi Wang; Ting Wu; Wei Li; Changpeng Qiu; Xuefeng Xu; Xi Zhang; Zhenhai Han; Xinzhong Zhang (Journal of Plant Growth Regulation, 2023)

Effects of instantaneous changes in temperature, light, and salinity on the dynamics of dissolved organic carbon release by Sargassum thunbergii - Zhi-Fang Zhao; Zhong-Jian Huang; Zuo-Deng Sun; Zheng-Yi Liu; Song Qin; Tong Han; Xin-Yu Qi; Xi-Yan Sun; Zhi-Hai Zhong (Marine Pollution Bulletin, 2023)

Investigation of heat stress on urban roadways for commuting children and mitigation strategies from the perspective of urban design - Yaru Meng; Junqi Wang; Chang Xi; Li Han; Zhuangbo Feng; Shi-Jie Cao (Urban Climate, 2023)

Spatial-temporal analysis method of ship traffic accidents involving data field: An evidence from risk evolution of ship collision - Qinghua Zhu; Yongtao Xi; Shenping Hu; Jianjun Wu; Bing Han (Ocean Engineering, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Brachypodium BdCHS is a homolog of Arabidopsis AtCHS involved in the synthesis of flavonoids and lateral root development - Jin Wang; Xiaolei Wang; Shifeng Zhao; Xiaoyu Xi; Jinlin Feng; Rong Han (Protoplasma, 2023)

A quantitative approach for sealing capacity evaluation of caprock in candidate of aquifer gas storage - Shanpo Jia; Meng Xu; Caoxuan Wen; Borui Li; Tuanhui Liu; Zengqiang Xi; Lin Han (Environmental Science and Pollution Research, 2023)

Evolution of sediment gravity flows in response to early Carboniferous subduction and closure of the West Junggar Basin, China - Jinjie Yong; Tingshan Zhang; Xi Zhang; Menglin Zheng; Yang Han; Dongsheng Ji; Shixin Li; Tao Wang (Marine and Petroleum Geology, 2023)

Shaking table experimental investigations on dynamic characteristics of CFRP cable dome - Weihong Qin; Han Gao; Zhuo Xi; Peng Feng; Yunjie Li (Engineering Structures, 2023)

Drug-Coated Balloon Treatment for Delayed Recanalization of Symptomatic Intracranial Artery Occlusion - Wei Zhao; Xi Chu; Yun Song; Jinping Zhang; Lili Sun; Meimei Zheng; Hao Yin; Jun Zhang; Wei Wang; Yao Meng; Ju Han (Translational Stroke Research, 2023)
Patients with medically refractory non-acute intracranial artery occlusion (ICAO) are difficult to treat. The optimal intervention for these patients is not known. We evaluated the feasibility and safety of drug-coated balloon (DCB) treatment for non-acute ICAO. Consecutive patients with symptomatic medically refractory atherosclerotic non-acute ICAO from January 2015 to July 2021 who underwent DCB treatment were retrospectively analyzed. The rates of stroke, transient ischemic attack, and death within 30 days and the follow-up results were evaluated. A total of 148 patients were enrolled in this study. The 30-day rate of stroke, transient ischemic attack, and death was 8.8%. During the 25.8 ± 15.8-month clinical follow-up period, the rate of outcome beyond 30 days was 4.7%. In the 66 patients with vessel imaging follow-up, 13.6% (9/66) had restenosis. The present study suggests that DCB dilatation is a feasible and effective alternative in carefully selected patients with symptomatic non-acute ICAO.

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

LiMYB108 is involved in floral monoterpene biosynthesis induced by light intensity in Lilium ‘Siberia’ - Yang Yun-Yao; Zhang Xi; Han Ming-Zheng; Hu Zeng-Hui; Wu Jing; Ma Nan; Leng Ping-Sheng; Zhou Xiao-Feng (Plant Cell Reports, 2023)

Optimal design and implementation of an amphibious bionic legged robot - Gang Wang; Kaixin Liu; Xinmeng Ma; Xi Chen; Shihao Hu; Qinyun Tang; Zhaojin Liu; Mingxuan Ding; Songjie Han (Ocean Engineering, 2023)

The Cretaceous (early Albian to early Campanian) biostratigraphy and palaeotemperature reconstruction of the eastern Tethys: Calcareous nannofossil evidence from southern Tibet, China - Yi Zhang; Xuan Liu; David K. Watkins; Mauro Daniel Rodrigues Bruno; Hanwei Yao; Kaibo Han; Huifang Guo; Shuaipeng Zhu; Xi Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A novel thermosensitive persulfate controlled-release hydrogel based on agarose/silica composite for sustained nitrobenzene degradation from groundwater - Shuxuan Wu; Sheng Deng; Fu Xia; Xu Han; Tianyu Ju; Han Xiao; Xiangjian Xu; Yu Yang; Yonghai Jiang; Beidou Xi (Journal of Hazardous Materials, 2023)

Effects of ultrasound-assisted slightly acidic electrolyzed water thawing on myofibrillar protein conformation and gel properties of chicken breasts - Dewei Kong; Chunli Quan; Qian Xi; Rongwei Han; Peng Li; Qijing Du; Yongxin Yang; Jingxin Sun; Mark Tamplin; Jun Wang (Food Chemistry, 2023)

Autochthonous Bacillus subtilis and Enterococcus faecalis improved liver health, immune response, mucosal microbiota and red-head disease resistance of yellow drum (Nibea albiflora) - Xi-Yue Ding; Cheng-Ye Wei; Zi-Yan Liu; Hong-Ling Yang; Fang Han; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Structural characterization and anti-inflammatory effects of an arabinan isolated from Rehmannia glutinosa Libosch. - Han Zhang; Yimin Yue; Qian Zhang; Lanyuan Liang; Chuanqiu Li; Ying Chen; Wei Li; Mingming Peng; Mengru Yang; Mantong Zhao; Xia Cao; Luyang Zhong; et al. (Carbohydrate Polymers, 2023)

Corrigendum to “Discovery and characterization of the flavonoids in Cortex Mori Radicis as naturally occurring inhibitors against intestinal nitroreductases” [Chem. Biol. Interact. 368 (2022) 110222] - Xi Chen; Yue Han; Lu Chen; Qian-Lin Tian; Yu-Ling Yin; Qi Zhou; Shi-Zhu Zang; Jie Hou (Chemico-Biological Interactions, 2023)

P2X7 receptor involved in antitumor activity of atractylenolide I in human cervical cancer cells - Yue Han; Can Bai; Xi-Meng He; Qing-Ling Ren (Purinergic Signalling, 2023)
Atractylenolide I (Atr-I) was found to sensitize a variety of human cancer cells in previous studies. Purinergic P2X7R plays important role in different cancers. However, whether Atr-I could generate antitumor activity in human cervical cancer cells and P2X7R get involved in this effect remain unclear. In this study, Hela (HPV 18 +) and SiHa (HPV 16 +) cells were treated with different doses of Atr-I. The results indicated that agonist and antagonist of P2X7 receptors, BzATP and JNJ-47965567 (JNJ), could suppress the proliferation of Hela and SiHa cells. Atr-I demonstrated a considerable antitumor effect in both human cervical cancer cells in vitro. Atr-I combined with P2X7R agonist, BzATP, restored Atr-I-induced growth inhibition in Hela cells but not in SiHa cells. However, the combinatorial treatment of P2X7R antagonist JNJ and Atr-I has an additive effect on cell growth inhibition in SiHa cells rather than in Hela cells. It implied that P2X7R would get involved in the anti-human cervical cancer cells effect of Atr-I.

Molecular alteration of the proteasome contributes to AD-like pathology in the brain of HFD-STZ diabetic rats - Han Gao; Ye Zhou; Peng-shuai Jin; Dong-gui Wu; Yu-na Wang; Xi Zhao; Bei Zhao (Metabolic Brain Disease, 2023)

Removal of collagen three-dimensional scaffold bubbles utilizing a vacuum suction technique - Lu-ming Nong; Yu-qing Jiang; Si-yuan zhou; Gong-ming Gao; Yong Ma; Xi-jia Jiang; Long Han (Cell and Tissue Banking, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

New study sheds light on the impressive intraspecific variation of Quaternary Asiatic black bears in China - Haiqian Hu; Haowen Tong; Haidong Yu; Fei Han; Jingsong Shi; Can Xiong; Yang Yu; Muhammad Ilyas; Xunqian Wang; Xi Chen (Quaternary International, 2023)

Two new monoterpenoids from the stems of Ephedra sinica - Chen He; Yan-gang Cao; Meng-nan Zeng; Yu-han Zhang; Ying-jie Ren; Yan-ling Liu; Xu Chen; Xi-ling Fan; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry Letters, 2023)

Nonlinear effects of internet development on chemical fertilizer application intensity: Macro evidence from China - Xi Chen; Lirong Xing; Kai Wang; Yue Zhang; Xiqiu Han (Journal of Cleaner Production, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

FSH-inhibited autophagy protects against oxidative stress in goat Sertoli cells through p62-Nrf2 pathway - Huaming Xi; Zhangtao Hu; Shuaiqi Han; Xinyu Liu; Liqiang Wang; Jianhong Hu (Theriogenology, 2023)

Response of dissolved organic carbon in rainwater during extreme rainfall period in megacity: Status, potential source, and deposition flux - Jie Zeng; Guilin Han; Shitong Zhang; Xuhuan Xiao; Yikai Li; Xi Gao; Di Wang; Rui Qu (Sustainable Cities and Society, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Coal-fired power plant CCUS project comprehensive benefit evaluation and forecasting model study - Jieping Han; Jiachun Li; Xi Tang; Lechen Wang; Xiaolong Yang; Zeqi Ge; Fei Yuan (Journal of Cleaner Production, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking - Chao Qi; Yueying Jin; Shengyu Cheng; Lei Di; Xin Wang; Minghui Zhang; Lingli Zhang; Xi-Ling Li; Yu Han; Qingkun Ma; Jun Zhe Min (Food Research International, 2023)

Multi-timescale and control-perceptive scheduling approach for flexible operation of power plant-carbon capture system - Han Xi; Mingjuan Zhu; Kwang Y. Lee; Xiao Wu (Fuel, 2023)

Patent mining on soil pollution remediation technology from the perspective of technological trajectory - Zefeng Qi; Yixin Han; Sandylove Afrane; Xi Liu; Mingqi Zhang; John Crittenden; Jian Lin Chen; Guozhu Mao (Environmental Pollution, 2023)

Detection of microplastics in domestic and fetal pigs’ lung tissue in natural environment: A preliminary study - Han Li; Zuosen Yang; Feng Jiang; Liang Li; Yansheng Li; Minmin Zhang; Zhenzhen Qi; Ruixue Ma; Yuanyuan Zhang; Jing Fang; Xi Chen; Yihang Geng; et al. (Environmental Research, 2023)

Cruise observation of the marine atmosphere and ship emissions in South China Sea: Aerosol composition, sources, and the aging process - Qibin Sun; Baoling Liang; Mingfu Cai; Yongyun Zhang; Hengjia Ou; Xue Ni; Xi Sun; Bo Han; Xuejiao Deng; Shengzhen Zhou; Jun Zhao (Environmental Pollution, 2023)

Spatio-temporal changes in daily extreme precipitation for the Lancang–Mekong River Basin - Qiongfang Li; Tianshan Zeng; Qihui Chen; Xingye Han; Xi Weng; Pengfei He; Zhengmo Zhou; Yao Du (Natural Hazards, 2023)

Origin of boron and lithium-rich salt lakes in center of Tibetan- plateau: Evidence from B and Cl isotopes - Yongsheng Du; Ji Long Han; Xi Ying Zhang (Applied Geochemistry, 2023)

Sea ice image classification based on ResFPG network and heterogeneous data fusion - Yanling Han; Xi Shi; Jing Wang; Yun Zhang; Zhonghua Hong; Zhenling Ma; Ruyan Zhou (International Journal of Remote Sensing, 2022)

Causal gene identification and desirable trait recreation in goldfish - Peng Yu; Yang Wang; Zhi Li; Hui Jin; Liang-Liang Li; Xiao Han; Zhong-Wei Wang; Xiao-Li Yang; Xi-Yin Li; Xiao-Juan Zhang; Li Zhou; Jian-Fang Gui (Science China Life Sciences, 2022)

A single QTL harboring multiple genetic variations leads to complicated phenotypic segregation in apple flesh firmness and crispness - Xianglong Yang; Bei Wu; Jing Liu; Zhongyan Zhang; Xuan Wang; Haie Zhang; Xuejun Ren; Xi Zhang; Yi Wang; Ting Wu; Xuefeng Xu; Zhenhai Han; et al. (Plant Cell Reports, 2022)

Associations of essential element serum concentrations with autism spectrum disorder - Jing Wu; Dongfang Wang; Lailai Yan; Meixiang Jia; Jishui Zhang; Songping Han; Jisheng Han; Jingyu Wang; Xi Chen; Rong Zhang (Environmental Science and Pollution Research, 2022)

Study on the Design and Experimental Research on a Bionic Crab Robot with Amphibious Multi-Modal Movement - Xi Chen; Jiawei Li; Shihao Hu; Songjie Han; Kaixin Liu; Biye Pan; Jixin Wang; Gang Wang; Xinmeng Ma (Journal of Marine Science and Engineering, 2022)
Bionic amphibious robots are the intersection of biology and robotics; they have the advantages of environmental adaptability and maneuverability. An amphibious robot that combines walking and swimming move modes inspired by a crab (Portunus) is presented in this article. The outstanding characteristic of the robot is that its environmental adaptability relies on the bionic multi-modal movement, which is based on two modular bionic swimming legs and six modular walking legs. We designed the biomimetic crab robot based on the biological observation results. The design, analysis, and simulation of its structure and motion parameters are introduced in this paper. The swimming propulsion capability and the walking performance are verified through indoor, pool, and seaside experiments. In conclusion, the designed bionic crab robot provides a platform with practical application capabilities in amphibious environment detection, concealed reconnaissance, and aquaculture.

Geology, fluid inclusion and H–O–C isotope geochemistry of the Doranasai gold deposit, Chinese Altai: implications for ore genesis - Xun Li; Xiaohua Deng; Wenxiang Liu; Abulimiti Aibai; Xi Chen; Shen Han; Yanshuang Wu; Yanjing Chen (International Journal of Earth Sciences, 2022)

Degradation of carbamazepine by high-voltage direct current gas–liquid plasma with the addition of H2O2 and Fe2+ - Jinming Yu; Weiwen Yan; Bin Zhu; Zimu Xu; Shuheng Hu; Wenhao Xi; Yan Lan; Wei Han; Cheng Cheng (Environmental Science and Pollution Research, 2022)

Association between short-term exposure to ambient PM1 and PM2.5 and forced vital capacity in Chinese children and adolescents - Han Wu; Yingxiu Zhang; Jing Wei; Pascal Bovet; Min Zhao; Wenhui Liu; Bo Xi (Environmental Science and Pollution Research, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Putative role of corazonin in the ovarian development of the swimming crab Portunus trituberculatus - Shisheng Tu; Fuqiang Ge; Yaoyao Han; Mengen Wang; Xi Xie; Dongfa Zhu (Frontiers in Marine Science, 2022)
Corazonin (Crz) is a neuropeptide that widely distributed in insects and crustaceans. The Crz is proposed to have pleiotropic functions in insects, but its physiological roles in crustaceans are poorly understood. In the present study, Crz and its putative receptor ( CrzR ) were identified from the swimming crab, Portunus trituberculatus , and their interaction was validated using the Dual-Luciferase reporter assay system. Tissue distribution analysis showed the PtCrz was mainly derived from center nerve system, while its receptor was highly expressed in Y-organ, the main site for ecdysteroids synthesis. Exposure of YO to synthetic Crz and CrzR dsRNA respectively led to the transcriptional changes of two ecdysteroidogenesis genes, further indicating a putative role of Crz signaling on ecdysteroids synthesis. During the ovarian development, the mRNA levels of PtCrz and PtCrzR increased significantly in vitellogenic stages, suggesting a potential role of Crz signaling in vitellogenesis. The hypothesis was further strengthened by in vitro experiments that the expression of vitellogenin ( Vg ), Vg receptor ( VgR ), cyclinB , and Cdc2 in ovary explants could be induced by synthetic Crz, whereas reduced by CrzR dsRNA. In addition, since 20-hydroxyecdysone also showed a stimulating effect on Vg expression, an indirect regulation of Crz signaling on ovarian development via ecdysteroids might also exist.

Rapid Characterization of Landslide-Debris Flow Chains of Geologic Hazards Using Multi-method Investigation: Case Study of the Tiejiangwan LDC - Kun He; Bo Liu; Xiewen Hu; Ruichen Zhou; Chuanjie Xi; Guotao Ma; Mei Han; You Li; Gang Luo (Rock Mechanics and Rock Engineering, 2022)

P2X7/P2X4 Receptors Mediate Proliferation and Migration of Retinal Microglia in Experimental Glaucoma in Mice - Meng-Xi Xu; Guo-Li Zhao; Xin Hu; Han Zhou; Shu-Ying Li; Fang Li; Yanying Miao; Bo Lei; Zhongfeng Wang (Neuroscience Bulletin, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

The pharmacokinetics of tacrolimus in peripheral blood mononuclear cells and limited sampling strategy for estimation of exposure in renal transplant recipients - Xi-Han Wang; Kun Shao; Hui-Min An; Xiao-Hui Zhai; Pei-Jun Zhou; Bing Chen (European Journal of Clinical Pharmacology, 2022)

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Correction to: Effectiveness of Newmark‑based sampling strategy for coseismic landslide susceptibility mapping using deep learning, support vector machine, and logistic regression - Chuanjie Xi; Mei Han; Xiewen Hu; Bo Liu; Kun He; Gang Luo; Xichao Cao (Bulletin of Engineering Geology and the Environment, 2022)

Effectiveness of Newmark-based sampling strategy for coseismic landslide susceptibility mapping using deep learning, support vector machine, and logistic regression - Chuanjie Xi; Mei Han; Xiewen Hu; Bo Liu; Kun He; Gang Luo; Xichao Cao (Bulletin of Engineering Geology and the Environment, 2022)

Enhanced genome editing to ameliorate a genetic metabolic liver disease through co-delivery of adeno-associated virus receptor - Shuming Yin; Lie Ma; Tingting Shao; Mei Zhang; Yuting Guan; Liren Wang; Yaqiang Hu; Xi Chen; Honghui Han; Nan Shen; Wenjuan Qiu; Hongquan Geng; et al. (Science China Life Sciences, 2022)

Evaluation of the effects of three different cooling methods on the dynamic mechanical properties of thermal-treated sandstone - Lifeng Fan; Han Li; Yan Xi (Bulletin of Engineering Geology and the Environment, 2022)

Cortical development coupling between surface area and sulcal depth on macaque brains - Xiao Li; Songyao Zhang; Xi Jiang; Shu Zhang; Junwei Han; Lei Guo; Tuo Zhang (Brain Structure and Function, 2022)

One-Way Intestinal Perfusion of PVP/VA–Poloxamer 188–Curcuma longa L. Extract Solid Dispersion in Rats In Vivo and Its Effect on HSC–T6 Cell Proliferation - Jie Gao; Yi Shi; Yunfeng Han; Xi Tang; Ruohong Bi; Lin Pan; Xianrong Lai (AAPS PharmSciTech, 2022)

Susceptibility of patients with chronic obstructive pulmonary disease to heart rate difference associated with the short-term exposure to metals in ambient fine particles: A panel study in Beijing, China - Ke Gao; Xi Chen; Xiaoying Li; Hanxiyue Zhang; Mengxiao Luan; Yuan Yao; Yifan Xu; Teng Wang; Yiqun Han; Tao Xue; Junxia Wang; Mei Zheng; et al. (Science China Life Sciences, 2022)

SbbHLH85, a bHLH member, modulates resilience to salt stress by regulating root hair growth in sorghum - Yushuang Song; Simin Li; Yi Sui; Hongxiang Zheng; Guoliang Han; Xi Sun; Wenjing Yang; Hailian Wang; Kunyang Zhuang; Fanying Kong; Qingwei Meng; Na Sui (Theoretical and Applied Genetics, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

Chemical constituent from the peel of Trichosanthes kirilowii Maxim and their NF-κB inhibitory activity - Xi Lei; Nan Li; Zisong Bai; Jingrui Di; Han Zhang; Pengzhi Dong; Peng Zhang (Natural Product Research, 2021)

Functional analysis of rice OSCA genes overexpressed in the arabidopsis osca1 mutant due to drought and salt stresses - Yuanjun Zhai; Zhaohong Wen; Wenqi Fang; Yinxing Wang; Chao Xi; Jin Liu; Heping Zhao; Yingdian Wang; Shengcheng Han (Transgenic Research, 2021)

Effects of Dietary Inclusion of Clostridium autoethanogenum Protein on the Growth Performance and Liver Health of Largemouth Bass (Micropterus salmoides) - Qisheng Lu; Longwei Xi; Yulong Liu; Yulong Gong; Jingzhi Su; Dong Han; Yunxia Yang; Junyan Jin; Haokun Liu; Xiaoming Zhu; Shouqi Xie (Frontiers in Marine Science, 2021)
Clostridium autoethanogenum protein (CAP) is a novel protein source for aqua-feeds. The present study aimed to investigate the effects of dietary CAP on growth performance, immunity, and liver health status of juvenile largemouth bass ( Micropterus salmoides ). Four isonitrogenous and isolipid experimental diets were formulated to replace 0% (D1, control), 25% (D2), 50% (D3), and 75% (D4) of fish meal by CAP. Fish (15.05 ± 0.08 g) were randomly fed one of four experimental diets for 8 weeks. The results showed that weight gain (WG), specific growth rate (SGR), feeding rate (FR), viscerosomatic index (VSI), and hepatosomatic index (HSI) of the D4 group were significantly lower than D1, D2, and D3 groups ( P < 0.05). With the increase of substitution level, the total antioxidant capacity (T-AOC) of liver tissue was significantly decreased, while the plasma alkaline phosphatase (AKP) activity was significantly increased ( P < 0.05). Plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were significantly higher in D3 and D4 groups than in D1 and D2 groups ( P < 0.05). Replacing 50 or 75% fish meal by CAP significantly induced the transcription level of apoptosis-promoting genes ( bcl-2 -associated death protein [ bad ] and bcl-2 -assoxicated × protein; bag [ bax ]), anti-apoptosis-related genes (tumor protein 53 [p53 ] and b-cell lymphoma-2 [ bcl-2 ]), and the apoptotic Caenorhabditis elegans ( C. elegans ) death gene-3 like caspases (cysteine-aspartic proteases-3 [ caspase-3 ], cysteine-aspartic proteases-8 [ caspase-8 ], cysteine-aspartic proteases-9 [ caspase-9 ], and cysteine-aspartic proteases-10 [ caspase-10 ]) in liver, while suppressed the gene expression of the inflammatory factors [interleukin-1β ( il-1 β), interleukin-8 ( il-8 ), and tumor necrosis factor, tnf ] in head kidney. At the same time, dietary inclusion of CAP elevated the protein expression of bcl-2, autophagy microtubule-associated protein light chain 3A/B (LC3A/B-I), and LC3A/B-II by inhibiting the phosphorylation of the mammalian target of rapamycin (mTOR; P < 0.05). Moreover, the apoptosis rate of the D3 and D4 groups was significantly increased ( P < 0.05). Taken together, these results indicated that the optimal level of CAP-replacing fish meal should be <50% that has no negative effect on the growth performance and liver health of juvenile largemouth bass. In addition, excessive CAP inclusion may damage liver health by activating autophagy and apoptosis signaling pathways.

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

Long-term high-intensity interval training increases serum neurotrophic factors in elderly overweight and obese Chinese adults - Xi Li; Tianyu Han; Xu Zou; Han Zhang; Wenpin Feng; Han Wang; Yulin Shen; Li Zhang; Guoliang Fang (European Journal of Applied Physiology, 2021)

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs - Hyo-Jin Paek; Zhao-Bo Luo; Hak-Myong Choe; Biao-Hu Quan; Kai Gao; Sheng-Zhong Han; Zhou-Yan Li; Jin-Dan Kang; Xi-Jun Yin (Transgenic Research, 2021)

Health and economic impacts from PM2.5 pollution transfer attributed to domestic trade in China: a provincial-level analysis - Xueyuan Hu; Han Sun; Xi Luo; Shan Ni; Yingying Yan (Environmental Science and Pollution Research, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Geochronology and geochemistry of late Jurassic–Early Cretaceous volcanic rocks in the southern Great Xing’an range, NE China: constraints for late Mesozoic tectono-magmatic evolution - Shi-Jiong Han; Xi Wang; Xin Wang; Yan Wang; Yang Zhang (International Geology Review, 2021)

Cladosporine A, a new indole diterpenoid alkaloid with antimicrobial activities from Cladosporium sp. - Xue Han; Xue-Feng Bao; Chuan-Xi Wang; Jun Xie; Xiao-Jun Song; Ping Dai; Guo-Dong Chen; Dan Hu; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Mechanisms of niche‐neutrality balancing can drive the assembling of microbial community - Lixiao Wang; Maozhen Han; Xi Li; Bingbing Yu; Huading Wang; Amjed Ginawi; Kang Ning; Yunjun Yan (Molecular Ecology, 2021)
One hotspot of present community ecology is to uncover the mechanisms of community succession. In this study, two popular concepts, niche‐neutrality dynamic balancing and co‐occurrence network analysis, were integrated to investigate the dispersal dynamics of microbial communities in a freshwater river continuum in subtropical China. Results showed that when habitat conditions were mild and appropriate, such as in the clean upstream river, free of heavy pollution or long‐lasting extreme disturbances, stochastic processes could increase species diversities, and organize communities into relatively loosely linked and stable networks with higher modularity and more modules. However, when conditions became degraded under heavy pollution, the influence of neutrality diminished, and niche‐based selection imposed more constraints on communities and guided the assembling processes in certain directions: depleting species richness, strengthening interspecies connections and breaking boundaries of modules. Consequently, communities became more sensitive to fluctuations so as to deal with the harsh conditions efficiently. Another interesting finding was that, both as keystone taxa of communities, module hubs were mostly neutrally distributed generalists with high abundances, and were beneficial to many related operational taxonomic units. In contrast, connectors were less abundant and their distributions were more subjected to the environments. Therefore, connectors were probably responsible for the information transmission between microbial communities and environments, as well as between different modules, and thus could restrict the dispersal of microbes and guide the direction of community assembly.

Wolbachia and Spiroplasma could influence bacterial communities of the spider mite Tetranychus truncatus - Kun Yang; Han Chen; Xiao-Li Bing; Xue Xia; Yu-Xi Zhu; Xiao-Yue Hong (Experimental and Applied Acarology, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Comparative genomic analysis of superoxide dismutase (SOD) genes in three Rosaceae species and expression analysis in Pyrus bretschneideri - Guohui Li; Fei Hu; Yang Zhang; Yu Zhao; Han Wang; Tianzhe Chen; Xi Cheng; Yongping Cai (Physiology and Molecular Biology of Plants, 2021)

Molecular characteristics associated with ferroptosis in hepatocellular carcinoma progression - Zuo Fei; Yin Lijuan; Zhuang Jing; Yang Xi; Pan Yuefen; Han Shuwen (Human Cell, 2021)

Correction to: Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2020)

Ochratoxin A in human blood plasma samples from apparently healthy volunteers in Nanjing, China - Kai Fan; Xi Cheng; Wenbo Guo; Xing Liu; Zhiqi Zhang; Qi Yao; Dongxie Nie; Bing Yao; Zheng Han (Mycotoxin Research, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Long noncoding RNA LINC00520 accelerates the progression of colorectal cancer by serving as a competing endogenous RNA of microRNA-577 to increase HSP27 expression - Xi-Han Jin; Yong-Gang Hong; Peng Li; Li-Qiang Hao; Ming Chen (Human Cell, 2020)

Widespread Os-isotopically ultradepleted mantle domains in the Paleo-Asian oceanic upper mantle: evidence from the Paleozoic Tianshan ophiolites (NW China) - Xiao-Han Gong; Ji-Feng Xu; Xi-Jun Liu; Xiao-Xiao Huang; Zhi-Guo Zhang; Hai-Long Zhou; Zheng-Yu Yang; Wen-Xia Zhao (International Journal of Earth Sciences, 2020)

Preparation of non-sintered lightweight aggregates through co-mechanochemical treatment of oil-contaminated drill cuttings, circulation fluidized bed combustion fly ash, and quicklime - Xiaoyue Chen; Zhonghui Xu; Zhengzhen Yao; Qin Shuai; Zao Jiang; Xi Peng; Yu Li; Ran An; Xin Jiang; Han Li (Environmental Science and Pollution Research, 2020)

Lactate accelerates vascular calcification through NR4A1-regulated mitochondrial fission and BNIP3-related mitophagy - Yi Zhu; Xi-Qiong Han; Xue-Jiao Sun; Rui Yang; Wen-Qi Ma; Nai-Feng Liu (Apoptosis, 2020)

RNAi of the nuclear receptor HR3 suggests a role in the molting process of the spider mite Panonychus citri - Gang Li; Xun-Yan Liu; Xi Han; Jin-zhi Niu; Jin-Jun Wang (Experimental and Applied Acarology, 2020)

Targeting Two Antigens Associated with B-ALL with CD19-CD123 Compound Car T Cell Therapy - Lulu E. Yan; Hongyu Zhang; Masayuki Wada; Liu Fang; Jia Feng; Wenli Zhang; Qi Chen; Yuanzhen Cao; Kevin G. Pinz; Kevin H. Chen; Jessica C. Petrov; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

Inhibitory effects of curcumin on H2O2-induced cell damage and APP expression and processing in SH-SY5Y cells transfected with APP gene with Swedish mutation - Xi-Jun Song; He-Yan Zhou; Ya-Xuan Sun; Han-Chang Huang (Molecular Biology Reports, 2020)

The efficiency of sequential extraction of phosphorus in soil and sediment: insights from the oxygen isotope ratio of phosphate - Xue-Tie Lei; Han Zhang; Min Chen; Laodong Guo; Xi-Guang Zhang; Zhao-Hua Jiang; Ruth E. Blake; Zhi-Gang Chen (Journal of Soils and Sediments, 2020)

Anti- β -amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. - Yu-Xi Wang; Bin Lin; Le Zhou; Zhi-Yang Yan; Han Zhang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Identifying Unregulated Emissions from Conventional Diesel Self-Ignition and PPCI Marine Engines at Full Load Conditions - Xi Wang; Minfei Wang; Yue Han; Hanyu Chen (Journal of Marine Science and Engineering, 2020)
A study on unregulated emissions of a conventional diesel self-ignition and partial premixed compression ignition (PPCI) marine engine at full load condition was performed, respectively. In this work, PPCI was realized in a marine engine by blending 15% diesel with 85% light hydrocarbons (LHC). Gas chromatography-mass spectrometry (GC-MS) was used to detect and identify unregulated emissions, and the chemical formula and peak area of representative species were obtained. Furthermore, the unregulated emissions were classified and semi-quantitatively analyzed. The results show that the maximum in-cylinder pressure of PPCI is almost 11 bar lower than that of conventional diesel combustion, and the crank angle at that moment is also delayed by 2 °CA. Compared to conventional diesel combustion, the maximum pressure rise rate of PPCI is reduced by 3.5%, while the maximum heat release rate of PPCI increases by 23.5%. Further, PPCI produces fewer species in unregulated emissions, and their chemical formula are less complex than that of conventional diesel combustion. Compared to conventional diesel combustion, the relative concentration of alkane and organic components in PPCI decreases significantly, while ketone and ester increase.

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Crocin attenuates isoprenaline-induced myocardial fibrosis by targeting TLR4/NF-κB signaling: connecting oxidative stress, inflammation, and apoptosis - Weiyue Jin; Yuanyuan Zhang; Yurun Xue; Xue Han; Xuan Zhang; Zhihong Ma; Shijiang Sun; Xi Chu; Jie Cheng; Shengjiang Guan; Ziliang Li; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Negative regulation of cadmium tolerance in Arabidopsis by MMDH2 - Xi Wu; Yangyang Han; Xiangyu Zhu; Alia Shah; Wei Wang; Yibao Sheng; Tingting Fan; Shuqing Cao (Plant Molecular Biology, 2019)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

Microglial Depletion with Clodronate Liposomes Increases Proinflammatory Cytokine Levels, Induces Astrocyte Activation, and Damages Blood Vessel Integrity - Xiaoning Han; Qian Li; Xi Lan; Leena EL-Mufti; Honglei Ren; Jian Wang (Molecular Neurobiology, 2019)

Network pharmacology-based screening of the active ingredients and potential targets of the genus of Pithecellobium marthae (Britton & Killip) Niezgoda & Nevl for application to Alzheimer’s disease - Han Zhang; Zhi-Yang Yan; Yu-Xi Wang; Ming Bai; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Ferroptosis and Its Role in Diverse Brain Diseases - Abigail Weiland; Yamei Wang; Weihua Wu; Xi Lan; Xiaoning Han; Qian Li; Jian Wang (Molecular Neurobiology, 2019)

GIS-based landslide susceptibility mapping using hybrid integration approaches of fractal dimension with index of entropy and support vector machine - Ting-yu Zhang; Ling Han; Heng Zhang; Yong-hua Zhao; Xi-an Li; Lei Zhao (Journal of Mountain Science, 2019)

Carbon concentrations and their stable isotopic signatures in the upper Han River, China - Xi Han; Xiaoli Cheng; Siyue Li; Jie Yuan; Quanfa Zhang (Environmental Science and Pollution Research, 2019)

Cloning, expression, and characterization of a novel nitrilase, PaCNit, from Pannonibacter carbonis Q4.6 - Dejian Liu; Lijun Xi; Danyang Han; Ke Dou; Shijing Su; Jianguo Liu (Biotechnology Letters, 2019)

Vascularized composite allograft rejection is delayed by infusion of IFN-γ-conditioned BMSCs through upregulating PD-L1 - Yaojun Wang; Yunfeng Xi; Fu Han; Yang Liu; Na Li; Zhongliang Ren; Jiajie Xue; Lei Guo; Dahai Hu (Cell and Tissue Research, 2019)

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Development of a reverse genetics system for a feline panleukopenia virus - Nan Cheng; Yongkun Zhao; Qiuxue Han; Weijiao Zhang; Ji Xi; Yongle Yu; Hualei Wang; Guohua Li; Yuwei Gao; Songtao Yang; Weiquan Liu; Xianzhu Xia (Virus Genes, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

WRKY12 represses GSH1 expression to negatively regulate cadmium tolerance in Arabidopsis - Yangyang Han; Tingting Fan; Xiangyu Zhu; Xi Wu; Jian Ouyang; Li Jiang; Shuqing Cao (Plant Molecular Biology, 2019)

Evaluating Algeria’s social and economic development using a series of night-time light images between 1992 to 2012 - Xi Li; Lixian Zhao; Wenjun Han; Bouarouri Faouzi; Prosper Washaya; Xubing Zhang; Huazhong Jin; Chuanqing Wu (International Journal of Remote Sensing, 2018)

Screening and Mutation of Saccharomyces cerevisiae UV-20 with a High Yield of Second Generation Bioethanol and High Tolerance of Temperature, Glucose and Ethanol - Shi Yi; Xiao Zhang; Han-xin Li; Xiao-xia Du; Shao-wei Liang; Xi-hua Zhao (Indian Journal of Microbiology, 2018)

The evolution of tea spatial agglomeration in China: An analysis based on different geographical scales - Han-chu Liu; Jie Fan; Yu-xi Zeng; Wen-zhao Wang (Journal of Mountain Science, 2018)

Adjusting precipitation measurements from the TRwS204 automatic weighing gauge in the Qilian Mountains, China - Qin Zheng; Ren-sheng Chen; Chun-tan Han; Jun-feng Liu; Yao-xuan Song; Zhang-wen Liu; Yong Yang; Lei Wang; Xi-qiang Wang; Xiao-jiao Liu; Shu-hai Guo; Guo-hua Liu (Journal of Mountain Science, 2018)

Degradation of Phenol in Water Using a Novel Gas-Liquid Two-Phase Dielectric Barrier Discharge Plasma Reactor - Han Zhang; Yanan Liu; Xi Cheng; Ai Zhang; Xiang Li; Jinxia Liu; Shijie Cai; Cheng Yang; Stéphanid Ognier; Pan Li (Water, Air, & Soil Pollution, 2018)

Decoding Auditory Saliency from Brain Activity Patterns during Free Listening to Naturalistic Audio Excerpts - Shijie Zhao; Junwei Han; Xi Jiang; Heng Huang; Huan Liu; Jinglei Lv; Lei Guo; Tianming Liu (Neuroinformatics, 2018)

Coupling and decoupling effects of agricultural carbon emissions in China and their driving factors - Haibin Han; Zhangqi Zhong; Yu Guo; Feng Xi; Shuangliang Liu (Environmental Science and Pollution Research, 2018)

Neonatal Exposure to Low-Dose (1.2%) Sevoflurane Increases Rats’ Hippocampal Neurogenesis and Synaptic Plasticity in Later Life - Xi Chen; Xue Zhou; Lu Yang; Xu Miao; Di-Han Lu; Xiao-Yu Yang; Zhi-Bin Zhou; Wen-Bin Kang; Ke-Yu Chen; Li-Hua Zhou; Xia Feng (Neurotoxicity Research, 2018)

The ammonia-catalyzed release of glycoprotein N-glycans - Chengjian Wang; Meifang Yang; Xi Gao; Cheng Li; Zihua Zou; Jianli Han; Linjuan Huang; Zhongfu Wang (Glycoconjugate Journal, 2018)

Structural predication and antigenic analysis of Toxoplasma gondii ROP20 - Jian Zhou; Wanchun Wang; Pengxia Song; Lin Wang; Yali Han; Jingjing Guo; Zhen Hao; Xi Zhu; Qiong Zhou; Xiadong Du; Gang Lu; Shenyi He; et al. (Acta Parasitologica, 2018)
Toxoplasma gondii infects almost all the warm-blooded animals. ROP20 protein is expressed in the rhoptry of Toxoplasma gondii . In this study, the secondary structure of ROP20 was analyzed using SMART software. We constructed and analyzed the 3D model of ROP20 protein using SWISS-MODEL online procedure and Visual Molecular Dynamics (VMD) software. The structure analysis fully indicated that ROP20 protein is an important member of the ROP family. Furthermore, We used DNASTAR software and Epitope Database online service to analyze liner-B cell epitopes and T-cell epitopes of ROP20 protein. All the analysis results of ROP20 protein can provide positive information on treatment and vaccine for toxoplasmosis. Moreover, ROP20 gene was obtained from PCR, and a recombinant eukaryotic expression vector (pEGFP-C1-ROP20) was constructed in the following study. After restriction enzyme digestion, the constructed plasmid was transfected into HEK 293-T cells. The RT-PCR result indicated that the recombinant plasmid could transcribe successfully in HEK 293-T cell. The results of western blotting indicated the expressed proteins can be recognized by anti-STAg mouse sera.

NaCl impact on Kosteletzkya pentacarpos seedlings simultaneously exposed to cadmium and zinc toxicities - Ming-Xi Zhou; Hélène Dailly; Marie-Eve Renard; Rui-Ming Han; Stanley Lutts (Environmental Science and Pollution Research, 2018)

Extendable supervised dictionary learning for exploring diverse and concurrent brain activities in task-based fMRI - Shijie Zhao; Junwei Han; Xintao Hu; Xi Jiang; Jinglei Lv; Tuo Zhang; Shu Zhang; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2018)

Isolation and identification of Salmonella pullorum bacteriophage YSP2 and its use as a therapy for chicken diarrhea - Kunyuan Tie; Yuyu Yuan; Shiqing Yan; Xi Yu; Qiuyang Zhang; Huihui Xu; Yang Zhang; Jingmin Gu; Changjiang Sun; Liancheng Lei; Wenyu Han; Xin Feng (Virus Genes, 2018)

Yield enhancement strategies of rare pharmaceutical metabolites from endophytes - Fangxue Xu; Shiyuan Wang; Yujuan Li; Mengmeng Zheng; Xiaozhi Xi; Hui Cao; Xiaowei Cui; Hong Guo; Chunchao Han (Biotechnology Letters, 2018)

Iodine-Rich Herbs and Potassium Iodate Have Different Effects on the Oxidative Stress and Differentiation of TH17 Cells in Iodine-Deficient NOD.H-2h4 Mice - Cheng-han Gao; Jin-qiao Qu; Xi-yu Zhou; Tian-shu Gao (Biological Trace Element Research, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Subcritical n-hexane/isopropanol extraction of lipid from wet microalgal pastes of Scenedesmus obliquus - Xiaoyu Bian; Wenbiao Jin; Qiong Gu; Xu Zhou; Yuhe Xi; Renjie Tu; Song-Fang Han; Guo-Jun Xie; Shu-Hong Gao; Qilin Wang (World Journal of Microbiology and Biotechnology, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

Embodied water analysis for Hebei Province, China by input-output modelling - Siyuan Liu; Mengyao Han; Xudong Wu; Xiaofang Wu; Zhi Li; Xiaohua Xia; Xi Ji (Frontiers of Earth Science, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Raman spectroscopic study of synthetic pyrope–grossular garnets: structural implications - Wei Du; Baofu Han; Simon Martin Clark; Yichuan Wang; Xi Liu (Physics and Chemistry of Minerals, 2018)

(−)-Epicatechin, a Natural Flavonoid Compound, Protects Astrocytes Against Hemoglobin Toxicity via Nrf2 and AP-1 Signaling Pathways - Xi Lan; Xiaoning Han; Qian Li; Jian Wang (Molecular Neurobiology, 2017)

Phyllanthus emblica Linn. fruit extract potentiates the anticancer efficacy of mitomycin C and cisplatin and reduces their genotoxicity to normal cells in vitro - Xi-han Guo; Juan Ni; Jing-lun Xue; Xu Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

Effects of salvianolic acid B on L-type calcium channels and myocardial contractility in isolated rat ventricular myocytes and hERG K+ channels expressed in HEK293 cells - Qiongtao Song; Xue Han; Yuchong Xue; Tao Song; Xi Chu; Xuan Zhang; Yuanyuan Zhang; Ying Zhang; Jianping Zhang; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Commonly preserved and species-specific gyral folding patterns across primate brains - Xiao Li; Hanbo Chen; Tuo Zhang; Xiang Yu; Xi Jiang; Kaiming Li; Longchuan Li; Mir Jalil Razavi; Xianqiao Wang; Xintao Hu; Junwei Han; Lei Guo; et al. (Brain Structure and Function, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

EGCG protects against homocysteine-induced human umbilical vein endothelial cells apoptosis by modulating mitochondrial-dependent apoptotic signaling and PI3K/Akt/eNOS signaling pathways - Shumin Liu; Zhengwu Sun; Peng Chu; Hailong Li; Anil Ahsan; Ziru Zhou; Zonghui Zhang; Bin Sun; Jingjun Wu; Yalin Xi; Guozhu Han; Yuan Lin; et al. (Apoptosis, 2017)

Levels and distributions of organochlorine pesticides in the soil–groundwater system of vegetable planting area in Tianjin City, Northern China - Hong-Wei Pan; Hong-Jun Lei; Xiao-Song He; Bei-Dou Xi; Yu-Ping Han; Qi-Gong Xu (Environmental Geochemistry and Health, 2017)

Effects of rainfall regime and its character indices on soil loss at loessial hillslope with ephemeral gully - Yong Han; Fen-li Zheng; Xi-meng Xu (Journal of Mountain Science, 2017)

Successful treatment of accessory breast cancer with endocrine therapy - Chun-xi Wang; Shu-li Guo; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2017)

Correlation between status of epidermal growth factor receptor mutation and distant metastases of lung adenocarcinoma upon initial diagnosis based on 1063 patients in China - Hongwei Li; Jianzhong Cao; Xiaqin Zhang; Xing Song; Weili Wang; Sufang Jia; Zhengran Li; Haixia Jia; Xing Cao; Wei Zhou; Jianhong Lian; Songye Han; et al. (Clinical & Experimental Metastasis, 2017)

Signal sampling for efficient sparse representation of resting state FMRI data - Bao Ge; Milad Makkie; Jin Wang; Shijie Zhao; Xi Jiang; Xiang Li; Jinglei Lv; Shu Zhang; Wei Zhang; Junwei Han; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2016)

Alternative industrial carbon emissions benchmark based on input-output analysis - Mengyao Han; Xi Ji (Frontiers of Earth Science, 2016)

The destruction box is involved in the degradation of the NTE family proteins by the proteasome - Fei-Fei Huang; Ping-An Chang; Lan-Xi Sun; Wen-Zhen Qin; Li-Ping Han; Rui Chen (Molecular Biology Reports, 2016)

Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2016)

Canopy structure and light interception partitioning among shoots estimated from virtual trees: comparison between apple cultivars grown on different interstocks on the Chinese Loess Plateau - Wei-Wei Yang; Xi-Long Chen; Marc Saudreau; Xiao-Yun Zhang; Man-Rang Zhang; Hang-Kong Liu; Evelyne Costes; Ming-Yu Han (Trees, 2016)

The Synergistic Effect of Serine with Selenocompounds on the Expression of SelP and GPx in HepG2 Cells - Qin Wang; Li-cui Sun; Yi-qun Liu; Jia-xi Lu; Feng Han; Zhen-wu Huang (Biological Trace Element Research, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

β1-Adrenergic blocker bisoprolol reverses down-regulated ion channels in sinoatrial node of heart failure rats - Yuan Du; Junbo Zhang; Yutao Xi; Geru Wu; Ke Han; Xin Huang; Aiqun Ma; Tingzhong Wang (Journal of Physiology and Biochemistry, 2016)

Autoimmunity and dysmetabolism of human acquired immunodeficiency syndrome - Yan-Mei Huang; Xue-Zhi Hong; Jia-Hua Xu; Jiang-Xi Luo; Han-You Mo; Hai-Lu Zhao (Immunologic Research, 2016)

Enhanced degradation of trichloroethylene using bentonite-supported nanoscale Fe/Ni and humic acids - Shihe Wang; Yitong Han; Xi Cao; Dan Zhao; Dezhong Yang; Jiawei Chen (Environmental Chemistry Letters, 2016)

Temperature dependent defence of Nicotiana tabacum against Cucumber mosaic virus and recovery occurs with the formation of dark green islands - Feifei Zhao; Yanan Li; Lijuan Chen; Lisha Zhu; Han Ren; Honghui Lin; Dehui Xi (Journal of Plant Biology, 2016)

A disparate subset of double-negative T cells contributes to the outcome of murine fulminant viral hepatitis via effector molecule fibrinogen-like protein 2 - Di Wu; Hongwu Wang; Weiming Yan; Tao Chen; Ming Wang; Meifang Han; Zeguang Wu; Xiaojing Wang; Guo Ai; Dong Xi; Guanxin Shen; Xiaoping Luo; et al. (Immunologic Research, 2016)

Erratum to: Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Salt-Rich Selenium for Prevention and Control Children with Kashin–Beck Disease: a Meta-analysis of Community-Based Trial - Fang-fang Yu; Jing Han; Xi Wang; Hua Fang; Huan Liu; Xiong Guo (Biological Trace Element Research, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

NK cell-based cancer immunotherapy: from basic biology to clinical application - Yang Li; Jie Yin; Ting Li; Shan Huang; Han Yan; JianMei Leavenworth; Xi Wang (Science China Life Sciences, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Microstructural and mineral analysis on the fault gouge in the coseismic shear zone of the 2008 M w 7.9 Wenchuan earthquake - Ren-mao Yuan; Bing-liang Zhang; Xi-wei Xu; Chuan-yong Lin; Zhu-jun Han (International Journal of Earth Sciences, 2015)

Data-driven analysis of functional brain interactions during free listening to music and speech - Jun Fang; Xintao Hu; Junwei Han; Xi Jiang; Dajiang Zhu; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

Mapping of regional soil salinities in Xinjiang and strategies for amelioration and management - Fei Wang; Xi Chen; Geping Luo; Qifei Han (Chinese Geographical Science, 2015)

The expression level of anthocyanidin synthase determines the anthocyanin content of crabapple (Malus sp.) petals - Jie Zhang; Zhen-yun Han; Ji Tian; Xi Zhang; Ting-ting Song; Yun-cong Yao (Acta Physiologiae Plantarum, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Sclareol production in the moss Physcomitrella patens and observations on growth and terpenoid biosynthesis - Xi-Wu Pan; Lei Han; Yu-Hua Zhang; Dong-Fang Chen; Henrik Toft Simonsen (Plant Biotechnology Reports, 2015)

Carbon stock and its responses to climate change in C entral A sia - Chaofan Li; Chi Zhang; Geping Luo; Xi Chen; Bagila Maisupova; Abdullo A. Madaminov; Qifei Han; Bekmamat M. Djenbaev (Global Change Biology, 2015)
Central Asia has a land area of 5.6 × 10 6 km 2 and contains 80–90% of the world's temperate deserts. Yet it is one of the least characterized areas in the estimation of the global carbon (C) stock/balance. This study assessed the sizes and spatiotemporal patterns of C pools in Central Asia using both inventory (based on 353 biomass and 284 soil samples) and process‐based modeling approaches. The results showed that the C stock in Central Asia was 31.34–34.16 Pg in the top 1‐m soil with another 10.42–11.43 Pg stored in deep soil (1–3 m) of the temperate deserts. They amounted to 18–24% of the global C stock in deserts and dry shrublands. The C stock was comparable to that of the neighboring regions in Eurasia or major drylands around the world (e.g. Australia). However, 90% of Central Asia C pool was stored in soil, and the fraction was much higher than in other regions. Compared to hot deserts of the world, the temperate deserts in Central Asia had relatively high soil organic carbon density. The C stock in Central Asia is under threat from dramatic climate change. During a decadal drought between 1998 and 2008, which was possibly related to protracted La Niña episodes, the dryland lost approximately 0.46 Pg C from 1979 to 2011. The largest C losses were found in northern Kazakhstan, where annual precipitation declined at a rate of 90 mm decade −1 . The regional C dynamics were mainly determined by changes in the vegetation C pool, and the SOC pool was stable due to the balance between reduced plant‐derived C influx and inhibited respiration.

Effect of culturing conditions on the expression of key enzymes in the proteolytic system of Lactobacillus bulgaricus - Jun-cai Hou; Fei Liu; Da-xi Ren; Wei-wei Han; Yue-ou Du (Journal of Zhejiang University-SCIENCE B, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

Energy budget over seasonal snow surface at an open site and beneath forest canopy openness during the snowmelt period in western Tianshan Mountains, China - Heng Lu; Wen-shou Wei; Mingzhe Liu; Xi Han; Wen Hong (Journal of Mountain Science, 2015)

Transgenerational and within-generational induction of defensive morphology in Brachionus calyciflorus (Rotifera): importance of maternal effect - Xu Wang Yin; Nai Xi Zhao; Bo Han Wang; Wen Jie Li; Zheng Nan Zhang (Hydrobiologia, 2015)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Observations and modeling of incoming longwave radiation to snow beneath forest canopies in the west Tianshan Mountains, China - Heng Lu; Wen-shou Wei; Ming-zhe Liu; Xi Han; Wen Hong (Journal of Mountain Science, 2014)

Local-scale systems input-output analysis of embodied water for the Beijing economy in 2007 - Mengyao Han; Shan Guo; Hui Chen; Xi Ji; Jiashuo Li (Frontiers of Earth Science, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Exploring how extracellular electric field modulates neuron activity through dynamical analysis of a two-compartment neuron model - Guo-Sheng Yi; Jiang Wang; Xi-Le Wei; Kai-Ming Tsang; Wai-Lok Chan; Bin Deng; Chun-Xiao Han (Journal of Computational Neuroscience, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

A fracture enhancement method based on the histogram equalization of eigenstructure-based coherence - Xi-Ying Dou; Li-Guo Han; En-Li Wang; Xue-Hua Dong; Qing Yang; Gao-Han Yan (Applied Geophysics, 2014)

Differential expression of carotenoid-related genes determines diversified carotenoid coloration in flower petal of Osmanthus fragrans - Yuanji Han; Xiaohui Wang; Weicai Chen; Meifang Dong; Wangjun Yuan; Xi Liu; Fude Shang (Tree Genetics & Genomes, 2014)

Fluid inclusion and isotope geochemistry of the Yangla copper deposit, Yunnan, China - Xi-An Yang; Jia-Jun Liu; Long-Bo Yang; Si-Yu Han; Xiao-Ming Sun; Huan Wang (Mineralogy and Petrology, 2014)

Metabolomics study of type 2 diabetes using ultra-performance LC-ESI/quadrupole-TOF high-definition MS coupled with pattern recognition methods - Ai-hua Zhang; Hui Sun; Guang-li Yan; Ye Yuan; Ying Han; Xi-jun Wang (Journal of Physiology and Biochemistry, 2014)

Survey of encoding and decoding of visual stimulus via FMRI: an image analysis perspective - Mo Chen; Junwei Han; Xintao Hu; Xi Jiang; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2014)

Metamorphism and microstructure of seasonal snow: Single layer tracking in Western Tianshan, China - Wen Hong; Wen-shou Wei; Ming-zhe Liu; Heng Lu; Xi Han; Yan-wei Zhang (Journal of Mountain Science, 2014)

Differences in oxygen-18 and deuterium content of throughfall and rainfall during different flood events in a small headwater watershed - Simin Qu; Minmin Zhou; Peng Shi; Han Liu; Weimin Bao; Xi Chen (Isotopes in Environmental and Health Studies, 2014)

Effects of orthodontic load on the periodontium of autogenously transplanted teeth in beagle dogs - Lu Lu; Hui-fang Sun; Han Xue; Jing Guo; Yang-xi Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Optimization of extraction of phenolics from leaves of Ficus virens - Xiao-xin Chen; Xiao-bing Wu; Wei-ming Chai; Hui-ling Feng; Yan Shi; Han-tao Zhou; Qing-xi Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Two endosymbiotic bacteria, Wolbachia and Arsenophonus, in the brown planthopper Nilaparvata lugens - Lv-Yu Qu; Yi-Han Lou; Hai-Wei Fan; Yu-Xuan Ye; Hai-Jian Huang; Meng-Qi Hu; Ya-Ni Zhu; Chuan-Xi Zhang (Symbiosis, 2013)

Bioreducible Polypeptide Containing Cell-Penetrating Sequence for Efficient Gene Delivery - Si Chen; Kai Han; Juan Yang; Qi Lei; Ren-Xi Zhuo; Xian-Zheng Zhang (Pharmaceutical Research, 2013)

Molecular and immunohistochemical characterization of the chitinase gene from Pieris rapae granulovirus - Seunghan Oh; Dong Hyun Kim; Bharat Bhusan Patnaik; Yong Hun Jo; Mi Young Noh; Hyo Jeong Lee; Kwang Ho Lee; Kwang Ho Yoon; Wan-Jong Kim; Ju Young Noh; Heon Cheon Jeong; Yong Seok Lee; et al. (Archives of Virology, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Meta-Analysis of Functional Roles of DICCCOLs - Yixuan Yuan; Xi Jiang; Dajiang Zhu; Hanbo Chen; Kaiming Li; Peili Lv; Xiang Yu; Xiaojin Li; Shu Zhang; Tuo Zhang; Xintao Hu; Junwei Han; et al. (Neuroinformatics, 2013)

Functionalized single-walled carbon nanotubes cause reversible acute lung injury and induce fibrosis in mice - Yanli Zhang; Jiejie Deng; Yanxu Zhang; Feng Guo; Chenggang Li; Zhen Zou; Wen Xi; Jun Tang; Yang Sun; Peng Yang; Zongsheng Han; Dangsheng Li; et al. (Journal of Molecular Medicine, 2013)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Developmental changes in lysophospholipid receptor expression in rodent heart from near-term fetus to adult - Fang Wang; Jianfeng Hou; Bianmei Han; Yu Nie; Xiangfeng Cong; Shengshou Hu; Xi Chen (Molecular Biology Reports, 2012)

Should few retrieved oocytes be as an indication for intracytoplasmic sperm injection? - Qing-song Xi; Li-xia Zhu; Juan Hu; Li Wu; Han-wang Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Preparation of biodiesel catalysed by KF/CaO with ultrasound - Xi Chen; Wei-Wei Qian; Xiao-Ping Lu; Ping-Fang Han (Natural Product Research, 2012)

Bombyx mori nucleopolyhedrovirus ORF54, a viral desmoplakin gene, is associated with the infectivity of budded virions - Min-Juan Zhang; Cai-Hong Tian; Xiao-Ying Fan; Yi-Han Lou; Ruo-Lin Cheng; Chuan-Xi Zhang (Archives of Virology, 2012)

Association between MTHFR C677T polymorphism and osteonecrosis of the femoral head: a meta-analysis - Xi-fu Shang; Hong Su; Wei-wei Chang; Chen-cheng Wang; Qin Han; Zhi-wei Xu (Molecular Biology Reports, 2012)

Fetal exposure to bisphenol A affects the primordial follicle formation by inhibiting the meiotic progression of oocytes - Han-Qiong Zhang; Xi-Feng Zhang; Lian-Jun Zhang; Hu-He Chao; Bo Pan; Yan-Min Feng; Lan Li; Xiao-Feng Sun; Wei Shen (Molecular Biology Reports, 2012)

Expression of a Suaeda salsa Vacuolar H+/Ca2+ Transporter Gene in Arabidopsis Contributes to Physiological Changes in Salinity - Ning Han; Wenjun Lan; Xi He; Qun Shao; Baoshan Wang; Xinjie Zhao (Plant Molecular Biology Reporter, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

The calcium-sensing receptor promotes adipocyte differentiation and adipogenesis through PPARγ pathway - Yong-Han He; Ying He; Xi-Lu Liao; Yu-Cun Niu; Guan Wang; Chen Zhao; Liang Wang; Ming-Jie Tian; Ying Li; Chang-Hao Sun (Molecular and Cellular Biochemistry, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Aerobic swimming performance of juvenile Schizothorax chongi (Pisces, Cyprinidae) in the Yalong River, southwestern China - Zhiying Tu; Xi Yuan; Jingcheng Han; Xiaotao Shi; Yingping Huang; David Johnson (Hydrobiologia, 2011)

SiRNA against Fabp5 induces 3T3-L1 cells apoptosis during adipocytic induction - Xi Ma; Xia Ren; Pengfei Han; Shengdi Hu; Junjun Wang; Jingdong Yin (Molecular Biology Reports, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Precipitation extremes in a karst region: a case study in the Guizhou province, southwest China - Qiang Zhang; Chong-Yu Xu; Zengxin Zhang; Xi Chen; Zhaoqing Han (Theoretical and Applied Climatology, 2010)

Can the soil seed bank contribute to revegetation of the drawdown zone in the Three Gorges Reservoir Region? - Zhi-Jun Lu; Lian-Fa Li; Ming-Xi Jiang; Han-Dong Huang; Da-Chuan Bao (Plant Ecology, 2010)

Blockage of ceramide metabolism exacerbates palmitate inhibition of pro-insulin gene expression in pancreatic β-cells - Jun Guo; YingYing Qian; XiaoXue Xi; XiaoHan Hu; JianXi Zhu; Xiao Han (Molecular and Cellular Biochemistry, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Receptor mediation and nociceptin inhibition of bradykinin-induced plasma extravasation in the knee joint of the rat - Kumi Moriyama; Jia Liu; Yeon Jang; Yun Jeong Chae; Yan Wang; James Mitchell; Stefan Grond; Xiaokang Han; Yilei Xing; Guo-xi Xie; Pamela Pierce Palmer (Inflammation Research, 2009)

Advances in researches on the immune dysregulation and therapy of severe acute pancreatitis - Xi-ping Zhang; Han-qing Chen; Fang Liu; Jie Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Purification and characterization of a novel endo-β-1,4-glucanase from the thermoacidophilic Aspergillus terreus - Jianmin Gao; Haibo Weng; Yu Xi; Daheng Zhu; Shaoyin Han (Biotechnology Letters, 2008)

Complete nucleotide sequence of a new strain of Tobacco necrosis virus A infecting soybean in China and infectivity of its full-length cDNA clone - Dehui Xi; Jiang Li; Chenggui Han; Dawei Li; Jialin Yu; Xueping Zhou (Virus Genes, 2008)

Mechanism of acute pancreatitis complicated with injury of intestinal mucosa barrier - Xi-ping Zhang; Jie Zhang; Qiao-ling Song; Han-qin Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Heat shock proteins and p53 play a critical role in K+ channel-mediated tumor cell proliferation and apoptosis - Xiaobing Han; Fang Wang; Weixing Yao; Hui Xing; Danhui Weng; Xiaohong Song; Gang Chen; Ling Xi; Tao Zhu; Jianfeng Zhou; Gang Xu; Shixuan Wang; et al. (Apoptosis, 2007)

Downregulation of neuronal sodium channel subunits Nav1.1 and Nav1.6 in the sinoatrial node from volume-overloaded heart failure rat - Yuan Du; Xin Huang; Tingzhong Wang; Ke Han; Junbo Zhang; Yutao Xi; Geru Wu; Aiqun Ma (Pflügers Archiv - European Journal of Physiology, 2007)

The Spen Homolog Msx2-Interacting Nuclear Target Protein Interacts with the E2 Ubiquitin-Conjugating Enzyme UbcH8 - Junfeng Li; Jishu Wang; Xi Yang; Junlin Li; Hongyan Qin; Xiao Dong; Yangting Zhu; Liang Liang; Yingmin Liang; Hua Han (Molecular and Cellular Biochemistry, 2006)

Inhibition of mitochondria responsible for the anti-apoptotic effects of melatonin during ischemia-reperfusion - Yi-xiang Han; Sheng-hui Zhang; Xi-ming Wang; Jian-bo Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Oxidative stress and damage induced by abnormal free radical reactions and IgA nephropathy - Jia-xi Chen; Jun-fu Zhou; Han-chao Shen (Journal of Zhejiang University-SCIENCE B, 2005)

A historical examination on land desertification in North China - Ting-zhen Yan; Xi-bo Chen; Guang-hui Han (Chinese Geographical Science, 2001)

Estimating the population size with a behavioral response in capture-recapture experiment - Paul S.F. Yip; Liqun Xi; Anne Chao; Wen-Han Hwang (Environmental and Ecological Statistics, 2000)